Image forming apparatus and image forming method
By using a cleaning blade made of polyurethane resin, its surface is rich in F and Si, the problem of toner film forming and cleaning blade wear on the image retaining body surface is solved, and more efficient image formation and longer-lived cleaning blades are achieved plate.
Patent Information
- Application Number
- CN202410180459.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-04
- Filing Date
- 2024-02-18
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, toner film formation is prone to occur on the surface of the image holding body, and the wear of the cleaning blade is severe, resulting in a decrease in the efficiency and life of the image forming device.
The cleaning scraper made of polyurethane resin is used, and the total amount of F and Si within 200 nm of the surface contacting the image holding body accounts for more than 75% of the total amount of F and Si within 5 μm of the surface, thereby reducing friction and Toner film formation is inhibited.
The toner film formation on the surface of the image holding body is effectively suppressed, and the wear of the cleaning blade is slowed down, thereby improving the efficiency of the image forming device and the service life of the cleaning blade.
Smart Images

Figure CN119439675A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an image forming device and an image forming method. Background Art
[0002] In an image forming device (copier, fax machine, printer, etc.) using an electrophotographic method, a toner image formed on the surface of an image holder such as a photoreceptor is transferred to the surface of a recording medium and fixed to the recording medium, thereby forming an image. In addition, a cleaning blade is used to clean the outer peripheral surface of the image holder.
[0003] For example, Patent Document 1 discloses "a cleaning scraper for cleaning foreign matter such as residual powder, the cleaning scraper comprising: a scraper body, an edge of which can be pressed against a surface where the foreign matter remains; and a lubricating layer, which is arranged on the surface of the scraper body at least on the side opposite to the surface where the foreign matter remains, and the scraper body is set in a pressed state in which the edge and the lubricating layer are simultaneously pressed against the surface where the foreign matter remains."
[0004] Patent document 2 discloses "a cleaning scraper for removing residual colorant on an image carrier or a transfer body, the cleaning scraper having a contact portion at the front end of a base portion, the base portion having a Shore D hardness of 50 to 80, a dynamic friction coefficient of ASTM D 1894 of 0.4 or less, and a Shore A hardness of 1 to 70 or less, and a Heidon-type dynamic friction coefficient against polycarbonate of 1.2 or less at a friction speed of 2000 mm / min."
[0005] Patent Document 1: Japanese Patent Application Publication No. 2005-345493
[0006] Patent Document 2: Japanese Patent Application Publication No. 2010-102327 Summary of the invention
[0007] The object of the present invention is to provide an image forming device and an image forming method, in which the total amount of F and Si existing within 200nm from the surface in contact with the image holder is less than 75% of the total amount of F and Si existing within 5μm from the surface, and the formation of colorant film on the surface of the image holder is suppressed and the wear of the cleaning scraper is suppressed, compared with an image forming device and an image forming method having a cleaning scraper in which the total amount of F and Si existing within 200nm from the surface in contact with the image holder is less than 75%.
[0008] Means for solving the above-mentioned problems include the following.
[0009] <1> An image forming apparatus comprising:
[0010] Image holding body;
[0011] a charging member for charging the surface of the image holding member;
[0012] an electrostatic latent image forming member for forming an electrostatic latent image on the charged surface of the image holding member;
[0013] A developing member containing an electrostatic latent image developer containing a toner having toner particles, wherein a release agent existing in a region within 800 nm from the surface of the toner particles accounts for 70% or more of the entire release agent of the toner particles, and a melting temperature of the release agent is 65° C. or more and 80° C. or less, and an electrostatic latent image formed on the surface of the image holding member is developed into a toner image by the electrostatic latent image developer;
[0014] a transfer member that transfers the toner image formed on the surface of the image holding body to a surface of a recording medium; and
[0015] A cleaning device having a cleaning scraper which contacts and cleans the outer peripheral surface of the image holder and is made of a polyurethane resin, wherein the total amount of F and Si present within 200 nm from the surface in contact with the image holder accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface.
[0016] <2> The image forming apparatus according to <1>, wherein:
[0017] The releasing agent existing in a region within 800 nm from the surface of the toner particle accounts for 75% or more of the releasing agent in the entire toner particle.
[0018] <3> The image forming apparatus according to <1> or <2>, wherein:
[0019] The melting temperature of the release agent is 70° C. or higher and 75° C. or lower.
[0020] <4> The image forming apparatus according to any one of <1> to <3>, wherein:
[0021] The 100% modulus at 23° C. of the surface of the cleaning blade in contact with the image holding body is 11 MPa or more and 22 MPa or less.
[0022] <5> The image forming apparatus according to <4>, wherein:
[0023] The 100% modulus at 23° C. of the surface of the cleaning blade in contact with the image holding body is 15 MPa or more and 18 MPa or less.
[0024] <6> The image forming apparatus according to any one of <1> to <5>, wherein
[0025] In the cleaning blade, the total amount of F and Si present within 200 nm from the surface in contact with the image holding member accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface.
[0026] <7> The image forming apparatus according to any one of <1> to <6>, wherein
[0027] In the cleaning blade, a total amount of F and Si present on a surface in contact with the image holding member is 15 atm % or more.
[0028] <8> The image forming apparatus according to <7>, wherein:
[0029] In the cleaning blade, a total amount of F and Si present on a surface in contact with the image holding member is 18 atm % or more and 25 atm % or less.
[0030] <9> The image forming apparatus according to any one of <1> to <8>, wherein:
[0031] In the cleaning blade, the total amount of F and Si present at a position 50 nm from the surface in contact with the image holding member is 0.3 atm % or more.
[0032] <10> The image forming apparatus according to <9>, wherein:
[0033] In the cleaning blade, a total amount of F and Si present at a position 50 nm from a surface in contact with the image holding member is 1.0 atm % or more and 2.0 atm % or less.
[0034] <11> The image forming apparatus according to any one of <1> to <10>, wherein
[0035] The cleaning blade contains a silicone-based polymer in a surface layer that contacts the image holding member.
[0036] <12> The image forming apparatus according to any one of <1> to <11>, wherein
[0037] A product of a static pressing force NF and a pressing angle WA between the cleaning blade and the image holding member is 40° or more and 60° or less.
[0038] <13> An image forming method, comprising:
[0039] A charging process to charge the surface of the image holding body;
[0040] An electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the image holding member;
[0041] A developing step of developing the electrostatic latent image formed on the surface of the image holding member into a toner image by an electrostatic latent image developer, wherein the electrostatic latent image developer contains a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less;
[0042] a transfer step of transferring the toner image formed on the surface of the image holding body to the surface of a recording medium; and
[0043] The cleaning process involves contacting a cleaning blade with the peripheral surface of the image holder and cleaning it, wherein the cleaning blade is made of a polyurethane resin, and the total amount of F and Si within 200 nm of the surface in contact with the image holder accounts for more than 75% of the total amount of F and Si within 5 μm of the surface.
[0044] Effects of the Invention
[0045] According to the invention involved in <1>, there is provided an image forming apparatus in which the formation of colorant film on the surface of the image holder is suppressed and the wear of the cleaning blade is suppressed, compared to an image forming apparatus having a cleaning blade in which the total amount of F and Si existing within 200nm from the surface in contact with the image holder is less than 75% of the total amount of F and Si existing within 5μm from the surface.
[0046] According to the invention <2>, an image forming apparatus having excellent low-temperature fixing property of an image is provided, compared with an image forming apparatus in which the releasing agent present in the region within 800 nm from the surface of the toner particle is less than 75% of the releasing agent in the entire toner particle.
[0047] According to the invention involved in <3>, an image forming apparatus is provided that has excellent low-temperature fixing property of an image compared to an image forming apparatus in which the melting temperature of a release agent exceeds 75°C, and an image forming apparatus is provided that suppresses the formation of colorant film on the surface of an image retaining body compared to an image forming apparatus in which the melting temperature of a release agent is lower than 70°C.
[0048] According to the invention involved in <4> or <5>, an image forming device is provided in which the 100% modulus of the surface of the cleaning scraper in contact with the image retainer at 23°C is less than 11 MPa, and the streaky image defects caused by the partial lifting of the scraper are suppressed; and an image forming device is provided in which the 100% modulus of the surface of the cleaning scraper in contact with the image retainer at 23°C exceeds 22 MPa, and the colorant filming on the surface of the image retainer is suppressed.
[0049] According to the invention involved in <6>, there is provided an image forming device in which the formation of colorant film on the surface of the image holder is suppressed and the wear of the cleaning scraper is suppressed, compared to an image forming device having a cleaning scraper in which the total amount of F and Si existing within 200nm from the surface in contact with the image holder is less than 85% of the total amount of F and Si existing within 5μm from the surface.
[0050] According to the invention involved in <7> or <8>, there is provided an image forming device in which the formation of colorant film on the surface of the image retaining body is suppressed and the wear of the cleaning blade is suppressed, compared with an image forming device having a cleaning blade in which the total amount of F and Si present on the surface in contact with the image retaining body is less than 15 atm%.
[0051] According to the invention involved in <9> or <10>, there is provided an image forming device in which the formation of colorant film on the surface of the image retaining body is suppressed and the wear of the cleaning scraper over time is also suppressed, compared to an image forming device having a cleaning scraper in which the total amount of F and Si present at a position 50nm away from the surface in contact with the image retaining body is less than 0.3atm%.
[0052] According to the invention of <11>, there is provided an image forming apparatus in which toner filming on the surface of an image holder is suppressed and wear of the cleaning blade is suppressed, compared to an image forming apparatus having a cleaning blade whose surface layer in contact with the image holder contains a fluorine-based compound but does not contain a silicone-based polymer.
[0053] According to the invention involved in <12>, an image forming device is provided, in which the product of the static pressing force NF and the pressing angle WA between the cleaning scraper and the image retaining body is less than 40, and the image forming device is provided, in which the occurrence of colorant leakage at the contact position between the image retaining body and the cleaning scraper is suppressed; and an image forming device is provided, in which the occurrence of colorant filming on the surface of the image retaining body is further suppressed, in which the product of the pressing force NF and the pressing angle WA exceeds 60.
[0054] According to the invention involved in <13>, there is provided an image forming method in which colorant filming on the surface of the image holder is suppressed and wear of the cleaning scraper is suppressed, compared to an image forming method including a cleaning process using a cleaning scraper in which the total amount of F and Si present within 200nm from the surface in contact with the image holder is less than 75% of the total amount of F and Si present within 5μm from the surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Embodiments of the present invention will be described in detail with reference to the following drawings.
[0056] Figure 1 is a schematic cross-sectional view showing an example of a layer structure of an electrophotographic photoreceptor used in this embodiment;
[0057] Figure 2 is a schematic structural diagram showing an example of an image forming apparatus according to the present embodiment;
[0058] Figure 3 is a schematic structural diagram showing another example of the image forming apparatus involved in this embodiment;
[0059] Figure 4 It is a schematic diagram for explaining the pressing force of the cleaning blade with respect to the image holding member. DETAILED DESCRIPTION
[0060] Hereinafter, the present embodiment as an example of the present invention will be described. These descriptions and examples are for illustrating the embodiment and do not limit the scope of the embodiment.
[0061] In the numerical ranges recorded in stages in this embodiment, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical ranges recorded in this embodiment, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment.
[0062] In the present embodiment, the term "process" includes not only independent processes but also processes that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0063] While the embodiment is described with reference to the drawings in this embodiment, the structure of the embodiment is not limited to the structure shown in the drawings. In addition, the sizes of the components in each figure are conceptual, and the relative relationship between the sizes of the components is not limited to this.
[0064] In this embodiment, each component may include a plurality of corresponding substances. In this embodiment, when the amount of each component in the composition is mentioned, if there are a plurality of substances corresponding to each component in the composition, unless otherwise specified, it means the total amount of the plurality of substances present in the composition.
[0065] [Image forming apparatus]
[0066] The image forming device involved in this embodiment comprises: an image holder; a charging component for charging the surface of the image holder; an electrostatic latent image forming component for forming an electrostatic latent image on the surface of the charged image holder; a developing component for containing an electrostatic latent image developer containing a colorant having colorant particles, and developing the electrostatic latent image formed on the surface of the image holder into a colorant image by the electrostatic latent image developer; a transfer component for transferring the colorant image formed on the surface of the image holder to the surface of a recording medium; and a cleaning device having a cleaning scraper, which contacts and cleans the outer peripheral surface of the cleaning image holder.
[0067] In the toner particles, the releasing agent present in a region within 800 nm from the surface accounts for 70% or more of the releasing agent in the entire toner particles, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less.
[0068] The cleaning blade is made of polyurethane resin, and the total amount of F and Si present within 200 nm from the surface in contact with the image holding member accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.
[0069] With the above-described configuration, the image forming apparatus according to the present embodiment suppresses toner filming on the surface of the image holding member and suppresses abrasion of the cleaning blade. The reason for this is presumably as follows.
[0070] From the viewpoint of improving the low-temperature fixability of an image, a method of using a toner having toner particles with a low melting temperature wax concentrated in the surface layer (specifically, a toner in which the release agent present in the region within 800 nm from the surface of the toner particle accounts for more than 70% of the total release agent of the toner particle, and the melting temperature of the release agent is from 65°C to 80°C) has been studied. However, when using toner particles in which a low melting temperature wax is concentrated in the surface layer, toner filming is sometimes likely to occur on the surface of the image holder when an image with a low image density is repeatedly formed under a high temperature and high humidity environment. It is believed that this is because the toner particles in which the low melting temperature wax is concentrated in the surface layer as described above will become soft under a high temperature and high humidity environment, resulting in easy crushing. Furthermore, it is believed that this is because by repeatedly forming an image with a low image density, the toner particles present on the image holder will decrease, thereby increasing the pressure applied by the cleaning blade to one toner particle.
[0071] In contrast, a method of suppressing toner filming by adjusting a cleaning blade pressed against an image holder is conceivable. For example, a method of suppressing toner filming by improving the scraping property by adjusting the pressing force NF (gf / mm) or the pressing angle WA (°) of the cleaning blade can be cited. However, when the scraping property of the cleaning blade is improved, the wear of the cleaning blade is aggravated, resulting in a shortened life of the cleaning blade. Therefore, in addition to suppressing toner filming, it is also required to suppress the wear of the cleaning blade.
[0072] In contrast, in the image forming apparatus according to the present embodiment, a cleaning blade is used in which the total amount of F and Si present within 200 nm from the surface in contact with the image holder accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface. That is, in the cleaning blade, F and Si are concentrated near the contact portion with the image holder. By having at least one of F and Si at the contact portion, the friction of the cleaning blade is reduced and the state of the front end of the contact portion becomes stable. Thus, even when using toner particles that cause the wax with a low melting temperature as described above to be concentrated in the surface layer, when a low image density image is repeatedly formed under a high temperature and high humidity environment, toner filming on the surface of the image holder can be suppressed.
[0073] Furthermore, by the presence of at least one of F and Si at the contact portion, the friction of the cleaning blade is reduced, and the wear of the cleaning blade can be suppressed.
[0074] From the above, it is presumed that according to the image forming apparatus according to the present embodiment, toner filming on the surface of the image holding member can be suppressed, and wear of the cleaning blade can be suppressed.
[0075] (Toner)
[0076] The toner contained in the electrostatic latent image developer used in the image forming apparatus according to the present embodiment is described. The toner contains toner particles, in which the release agent present in the region within 800 nm from the surface of the toner particles accounts for more than 70% of the release agent in the entire toner particles, and the melting temperature of the release agent is more than 65° C. and less than 80° C.
[0077] The toner particles contain a release agent and may further contain a binder resin. Furthermore, the toner particles may further contain other internal additives such as a colorant.
[0078] -Release agent-
[0079] The melting temperature of the release agent is 65° C. to 80° C., for example, preferably 68° C. to 77° C., more preferably 70° C. to 75° C. When the melting temperature of the release agent is 80° C. or less, the low-temperature fixability of the image can be improved. On the other hand, when the melting temperature of the release agent is 65° C. or more, toner filming on the transfer belt surface can be suppressed.
[0080] The melting temperature of the release agent is determined from a DSC curve obtained by differential scanning calorimetry (DSC) according to the “melting peak temperature” described in the method for determining the melting temperature in JIS K-7121-1987 “Methods for determining transition temperatures of plastics”.
[0081] Regarding the release agent, 70% or more of all the release agent exists within 800 nm from the surface of the toner particles (hereinafter, the proportion of the release agent existing within 800 nm from the surface of the toner particles is also referred to as "surface layer proportion of the release agent").
[0082] The surface ratio of the release agent is 70% or more, for example, preferably 75% or more, more preferably 80% or more. The upper limit of the surface ratio of the release agent is preferably 100%. When the surface ratio of the release agent is 70% or more, the low temperature fixability of the image can be improved.
[0083] Here, the method for measuring the surface layer ratio of the release agent is described.
[0084] The measurement samples and images were prepared by the following method.
[0085] The toner is mixed with the epoxy resin and embedded in the epoxy resin to cure the epoxy resin. The cured product is cut using an ultrathin sectioning device (Ultracut UCT manufactured by Leica Corporation) to form a thin sheet sample with a thickness of more than 80 nm and less than 130 nm. Then, an ultra-high resolution field emission scanning electron microscope (FE-SEM. S-4800 manufactured by Hitachi High-Technologies Corporation) is used to obtain an SEM image of the thin sheet sample. In the SEM image, a cross section of a toner particle having a maximum length of more than 85% of the volume average particle size of the toner particle is selected, and the domain of the release agent is observed to determine the area of the release agent of the entire toner particle and the area of the release agent present in the region within 800 nm from the surface of the toner particle, and calculate the area ratio of the two (the area of the release agent present in the region within 800 nm from the surface of the toner particle / the area of the release agent of the entire toner particle). Then, the calculation is performed on 100 toner particles, and the average value is used as the surface ratio of the release agent.
[0086] The reason for selecting a colorant particle cross section whose maximum length is greater than 85% of the volume average particle size of the colorant particle is that a cross section less than 85% of the volume average particle size is predicted to be a cross section at the end of the colorant particle, and the state of the domain in the colorant particle will not be well reflected in the cross section at the end of the colorant particle.
[0087] As a control method for making the surface layer ratio of the release agent 70% or more, for example, there is a method of making the toner particles have a core-shell structure and using a release agent when forming the shell.
[0088] Examples of the release agent include hydrocarbon waxes such as paraffin wax, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.
[0089] As a release agent, for example, hydrocarbon wax is preferably used. Hydrocarbon wax is a wax having a hydrocarbon as a skeleton, and examples thereof include Fischer-Tropsch wax, polyethylene wax (wax having a polyethylene skeleton), polypropylene wax (wax having a polypropylene skeleton), paraffin wax (wax having a paraffin skeleton), microcrystalline wax, etc. Among them, as a hydrocarbon wax, from the viewpoint of fixability, for example, Fischer-Tropsch wax, polyethylene wax or polypropylene wax is preferred. And, for example, from the viewpoint of fixability, it is preferred that the toner particles contain a plurality of hydrocarbon waxes.
[0090] The ratio of the hydrocarbon wax to the total release agent is, for example, preferably 85 mass % or more, preferably 95 mass % or more, and more preferably 100 mass %.
[0091] The content of the release agent is, for example, preferably 1% by mass to 20% by mass, more preferably 3% by mass to 20% by mass, more preferably 3% by mass to 15% by mass, and even more preferably 5% by mass to 15% by mass, relative to the entire toner particles.
[0092] -Bonding resin-
[0093] As the binder resin, for example, a polyester resin is preferably used. The ratio of the polyester resin to the total binder resin is, for example, preferably 75% by mass or more, preferably 90% by mass or more, and more preferably 100% by mass.
[0094] As the polyester resin, for example, a known amorphous polyester resin can be cited. The polyester resin can use a crystalline polyester resin together with the amorphous polyester resin. However, the crystalline polyester resin is preferably used in a range of 2% by mass or more and 40% by mass or less (for example, more preferably 2% by mass or more and 20% by mass or less) relative to the entire binder resin.
[0095] The "crystallinity" of a resin refers to having a clear endothermic peak in differential scanning calorimetry (DSC) rather than a step-like change in endothermic value. Specifically, it means that the half width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min).
[0096] On the other hand, the "amorphous" nature of a resin means that the half width exceeds 10°C, the endothermic value shows a step-like change, or a clear endothermic peak cannot be confirmed.
[0097] Amorphous polyester resin
[0098] Examples of the non-crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. In addition, commercially available products or synthetic resins may be used as the non-crystalline polyester resin.
[0099] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof. Among these, aromatic dicarboxylic acids are preferred as the polycarboxylic acid.
[0100] The polycarboxylic acid may be used together with the dicarboxylic acid and a trivalent or higher carboxylic acid having a crosslinked structure or a branched structure. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof.
[0101] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0102] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among them, the polyol is preferably an aromatic diol or an alicyclic diol, and more preferably an aromatic diol.
[0103] As the polyol, a trivalent or higher polyol having a cross-linked structure or a branched structure may be used together with a diol. Examples of the trivalent or higher polyol include glycerol, trimethylolpropane, and pentaerythritol.
[0104] The polyols may be used alone or in combination of two or more.
[0105] The glass transition temperature (Tg) of the amorphous polyester resin is, for example, preferably 50° C. or higher and 80° C. or lower, and more preferably 50° C. or higher and 65° C. or lower.
[0106] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition start temperature" described in the method for determining the glass transition temperature in JIS K 7121-1987 "Determination of Transition Temperature of Plastics".
[0107] The weight average molecular weight (Mw) of the amorphous polyester resin is, for example, preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less.
[0108] The number average molecular weight (Mn) of the amorphous polyester resin is preferably, for example, 2,000 or more and 100,000 or less.
[0109] The molecular weight distribution Mw / Mn of the amorphous polyester resin is, for example, preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.
[0110] The weight average molecular weight and the number average molecular weight are measured by gel permeation chromatography (GPC). In the molecular weight measurement by GPC, GPC HLC-8120GPC manufactured by TOSOH CORPORATION is used as a measuring device, a TOSOH CORPORATION column TSKgel SuperHM-M (15 cm) is used, and THF solvent is used. The weight average molecular weight and the number average molecular weight are calculated using a molecular weight calibration curve prepared from a monodisperse polystyrene standard sample based on the measurement results.
[0111] The amorphous polyester resin is obtained by a known production method. Specifically, for example, the amorphous polyester resin is obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as necessary, and reacting while removing water and alcohol generated during condensation.
[0112] In addition, when the monomer of the raw material is insoluble or incompatible at the reaction temperature, a high boiling point solvent can be added as a cosolvent to dissolve it. In this case, the polycondensation reaction is carried out while the cosolvent is removed by distillation. In the case of the presence of a monomer with poor compatibility in the copolymerization reaction, for example, the monomer with poor compatibility can be condensed in advance with an acid or alcohol to be polycondensed with the monomer, and then polycondensed together with the main component.
[0113] Crystalline polyester resin
[0114] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. In addition, as the crystalline polyester resin, a commercially available product may be used, and a synthetic resin may also be used.
[0115] Here, since the crystalline polyester resin easily forms a crystal structure, for example, it is preferable to use a polycondensate of a polymerizable monomer having a linear aliphatic group rather than a polycondensate of a polymerizable monomer having an aromatic group.
[0116] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., having 1 to 5 carbon atoms) alkyl esters thereof.
[0117] The polycarboxylic acid may be used together with the dicarboxylic acid, and a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 or more and 5 or less) alkyl esters.
[0118] As the polycarboxylic acid, a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond can be used together with these dicarboxylic acids.
[0119] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0120] Examples of the polyol include aliphatic diols (e.g., linear aliphatic diols having a main chain portion having carbon atoms of 7 or more and 20 or less). Examples of the aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-docosanediol. Among them, examples of the aliphatic diols include 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.
[0121] As the polyol, a trivalent or higher alcohol having a cross-linked structure or a branched structure may be used together with the diol. Examples of the trivalent or higher alcohol include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0122] The polyols may be used alone or in combination of two or more.
[0123] Among them, the content of the aliphatic diol in the polyol is preferably 80 mol % or more, and preferably 90 mol % or more.
[0124] The melting temperature of the crystalline polyester resin is, for example, preferably 50° C. or higher and 100° C. or lower, more preferably 55° C. or higher and 90° C. or lower, and further preferably 60° C. or higher and 85° C. or lower.
[0125] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) in accordance with the "melting peak temperature" described in the method for determining the melting temperature in JIS K7121-1987 "Determination of Transition Temperatures of Plastics".
[0126] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably, for example, 6,000 or more and 35,000 or less.
[0127] Similar to the amorphous polyester resin, the crystalline polyester resin can be obtained by, for example, a well-known production method.
[0128] Here, the binder resin may be used together with the polyester resin and other binder resins. As other binder resins, for example, styrene (meth) acrylic resins are preferably used.
[0129] -Styrene (meth) acrylic resin-
[0130] Styrene (meth) acrylic resin is a copolymer obtained by copolymerizing at least a monomer having a styrene skeleton and a monomer having a (meth) acryloyl group. "(Meth) acrylic" includes both "acrylic" and "methacrylic". Furthermore, "(meth) acryloyl" includes both "acryloyl" and "methacryloyl".
[0131] Examples of monomers having a styrene skeleton (hereinafter referred to as "styrene-based monomers") include styrene, alkyl-substituted styrenes (e.g., α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), halogen-substituted styrenes (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), vinylnaphthalene, etc. The styrene-based monomers may be used alone or in combination of two or more.
[0132] Among them, as the styrene-based monomer, for example, styrene is preferred from the viewpoint of reactivity, controllability of reaction, and availability.
[0133] Examples of monomers having a (meth)acryloyl group (hereinafter referred to as "(meth)acrylic monomers") include (meth)acrylic acid and (meth)acrylic acid esters. Examples of (meth)acrylic acid esters include (meth)acrylic acid alkyl esters (e.g., n-methyl (meth)acrylate, n-ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, and n-octadecyl (meth)acrylate). (meth)acrylate, such as pentyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, etc.), aryl (meth)acrylate (for example, phenyl (meth)acrylate, biphenyl (meth)acrylate, diphenylethyl (meth)acrylate, tert-butylphenyl (meth)acrylate, terphenyl (meth)acrylate, etc.), dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, β-carboxyethyl (meth)acrylate, (meth)acrylamide, etc. The (meth)acrylic monomer may be used alone or in combination of two or more.
[0134] The copolymerization ratio of the styrene-based monomer and the (meth)acrylic-based monomer (based on mass, styrene-based monomer / (meth)acrylic-based monomer) is preferably, for example, 85 / 15 to 70 / 30.
[0135] From the viewpoint of suppressing the print-through of the image, the styrene (meth) acrylic resin preferably has a cross-linked structure. Examples of the styrene (meth) acrylic resin having a cross-linked structure include a cross-linked product obtained by copolymerizing and cross-linking at least a monomer having a styrene skeleton, a monomer having a (meth) acrylic skeleton, and a cross-linking monomer.
[0136] Examples of the crosslinkable monomer include bifunctional or higher-functional crosslinking agents.
[0137] Examples of the bifunctional crosslinking agent include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylenebis(meth)acrylamide, decanediol diacrylate, glycidyl(meth)acrylate, etc.), polyester di(meth)acrylate, and 2-([1'-methylpropyleneamino]carboxyamino)ethyl methacrylate.
[0138] Examples of the polyfunctional crosslinking agent include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc.), tetra(meth)acrylate compounds (e.g., tetramethylolmethane tetra(meth)acrylate, oligoester (meth)acrylate, etc.), 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, triallyl trimellitate, diallyl chlorendonate, etc.
[0139] The copolymerization ratio of the crosslinkable monomer to all monomers (based on mass, crosslinkable monomer / all monomers) is preferably, for example, 2 / 1000 to 30 / 1000.
[0140] From the viewpoint of suppressing the strike-through of an image, the weight average molecular weight of the styrene (meth) acrylic resin is, for example, preferably 30,000 to 200,000, preferably 40,000 to 100,000, and more preferably 50,000 to 80,000.
[0141] The weight average molecular weight of the styrene (meth) acrylic resin is a value measured by the same method as the weight average molecular weight of the polyester resin.
[0142] From the viewpoint of balancing the fluidity and storage properties of the colorant and suppressing the print-through of the image, the content of the styrene (meth) acrylic resin is preferably, for example, 10% by mass or more and 30% by mass or less, preferably 12% by mass or more and 28% by mass or less, and more preferably 15% by mass or more and 25% by mass or less, relative to the colorant particles.
[0143] Furthermore, other binding resins may be used simultaneously as the binding resin.
[0144] As other binder resins, for example, there can be mentioned vinyl resins composed of homopolymers of monomers such as styrenes (for example, styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (for example, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (for example, acrylonitrile, methacrylonitrile, etc.), vinyl ethers (for example, vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (for example, vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (for example, ethylene, propylene, butadiene, etc.), or copolymers formed by combining two or more of these monomers.
[0145] Other examples of binder resins include epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, modified rosins and other non-vinyl resins, mixtures thereof with the above-mentioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers under the coexistence of the above-mentioned resins.
[0146] These other binder resins may be used alone or in combination of two or more.
[0147] The content of the binder resin is, for example, preferably 40 mass % to 95 mass % inclusive, more preferably 50 mass % to 90 mass % inclusive, and further preferably 60 mass % to 85 mass % inclusive, based on the entire toner particles.
[0148] -Colorants-
[0149] Examples of the colorant include various pigments such as carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, vulcan orange, magenta, permanent red, brilliant carmine 3B, brilliant carmine 6B, Dupont Oil Red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose Bengal, aniline blue, ultramarine blue, copper oil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; and various dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, nigrosine-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based.
[0150] The coloring agent may be used alone or in combination of two or more.
[0151] The colorant may be a surface-treated colorant as required, or may be used together with a dispersant. Furthermore, a plurality of colorants may be used simultaneously.
[0152] The content of the colorant is, for example, preferably 1 mass % to 30 mass % inclusive, and more preferably 3 mass % to 15 mass % inclusive, based on the entire toner particles.
[0153] -Other additives-
[0154] Examples of other additives in the toner include well-known additives such as magnetic materials, charge control agents, and inorganic powders. These additives are contained in the toner particles as internal additives.
[0155] -Characteristics of toner particles-
[0156] The toner particles may be toner particles of a single-layer structure, or toner particles of a so-called core-shell structure composed of a core (core particle) and a coating layer (shell layer) coating the core, and preferably a core-shell structure. The toner particles of a core-shell structure preferably consist of a core composed of a binder resin and a colorant, and a coating layer composed of a binder resin and a release agent.
[0157] The volume average particle size (D50v) of the toner particles is, for example, preferably 2 μm or more and 10 μm or less, and more preferably 4 μm or more and 8 μm or less.
[0158] Various average particle diameters and various particle size distribution indices of the toner particles were measured using Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte solution was measured using ISOTON-II (manufactured by Beckman Coulter, Inc.).
[0159] During measurement, 0.5 mg to 50 mg of a measurement sample is added as a dispersant to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate), and this is added to 100 ml to 150 ml of an electrolyte.
[0160] The electrolyte in which the sample was suspended was dispersed by an ultrasonic disperser for 1 minute, and the particle size distribution of particles with a particle size ranging from 2 μm to 60 μm was measured by Coulter Multisizer II using an aperture of 100 μm. The number of particles to be sampled was 50,000.
[0161] The cumulative distribution of volume and number is plotted for the particle size range (channel) divided based on the measured particle size distribution from the small diameter side, and the particle size when the cumulative amount reaches 16% is defined as the volume particle size D16v and the number average particle size D16p, the particle size when the cumulative amount reaches 50% is defined as the volume average particle size D50v and the number average particle size D50p, and the particle size when the cumulative amount reaches 84% is defined as the volume particle size D84v and the number average particle size D84p.
[0162] Use them, by (D84v / D16v) 1 / 2 Calculate the volume average particle size distribution index (GSDv) from (D84p / D16p) 1 / 2 Calculate the number average particle size distribution index (GSDp).
[0163] The shape factor SF1 of the toner particles is, for example, preferably 110 or more and 150 or less, and more preferably 120 or more and 140 or less.
[0164] The shape factor SF1 is obtained by the following formula.
[0165] Formula: SF1 = (ML 2 / A)×(π / 4)×100
[0166] In the above formula, ML represents the absolute maximum length of the toner, and A represents the projected area of the toner.
[0167] Specifically, the shape factor SF1 is digitized mainly by analyzing a microscope image or a scanning electron microscope image using an image analyzer, and is calculated as follows: That is, an optical microscope image of particles scattered on the surface of a slide is introduced into a Luzex image analyzer using a camera, the maximum length and projected area of 100 particles are obtained, and the calculation is performed using the above formula to obtain the average value.
[0168] -External Additives-
[0169] The toner may contain an external additive in addition to the toner particles.
[0170] Examples of the external additive include inorganic particles. Examples of the inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2) n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.
[0171] The surface of the inorganic particles as an external additive is preferably subjected to a hydrophobic treatment, for example. The hydrophobic treatment is carried out, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and for example, a silane coupling agent, silicone oil, a titanate coupling agent, an aluminum coupling agent, etc. can be cited. They can be used alone or in combination of two or more.
[0172] The amount of the hydrophobizing agent is, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.
[0173] Examples of the external additives include resin particles (polystyrene, polymethyl methacrylate (PMMA), melamine resin, and the like), cleaning aids (for example, metal salts of higher fatty acids such as zinc stearate, and particles of fluorine-based high molecular weight bodies).
[0174] The amount of the external additive added is, for example, preferably 0.01% by mass or more and 5% by mass or less, and more preferably 0.01% by mass or more and 2.0% by mass or less, based on the toner particles.
[0175] -Method for producing toner-
[0176] The toner used in the image forming apparatus according to the present embodiment is produced by producing toner particles and, if the toner particles further contain an external additive, adding the external additive to the toner particles.
[0177] The toner particles can be produced by any of dry methods (e.g., kneading and pulverization methods) and wet methods (e.g., aggregation method, suspension polymerization method, dissolution suspension method, etc.). These methods are not particularly limited, and well-known methods can be used. Among them, it is preferred to obtain the toner particles by, for example, the aggregation method.
[0178] The following is a description of the details of each step of the aggregation method. In the following description, a method for obtaining toner particles containing a colorant is described, but a colorant can be used as needed. Of course, other additives besides the colorant can also be used.
[0179] ·Resin particle dispersion preparation process
[0180] First, a resin particle dispersion in which polyester resin particles serving as a binder resin are dispersed, a colorant dispersion in which colorant particles are dispersed, and a release agent particle dispersion in which release agent particles are dispersed are prepared.
[0181] The polyester resin particle dispersion is prepared by, for example, dispersing the polyester resin particles in a dispersion medium using a surfactant.
[0182] Examples of the dispersion medium used for the polyester resin particle dispersion include aqueous media.
[0183] Examples of the aqueous medium include water such as distilled water and deionized water; and alcohols, etc. These may be used alone or in combination of two or more.
[0184] Examples of surfactants include anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols. Among them, anionic surfactants and cationic surfactants are particularly useful. Nonionic surfactants may be used together with anionic surfactants or cationic surfactants.
[0185] The surfactant may be used alone or in combination of two or more.
[0186] As a method for dispersing polyester resin particles in a dispersion medium, for example, conventional dispersion methods using a rotary shearing homogenizer or a ball mill, a sand mill, a DYNO-MILL, etc. with a medium can be cited. In addition, the polyester resin particles can also be dispersed in a dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method refers to the following method: the resin to be dispersed is dissolved in a hydrophobic organic solvent that can dissolve the resin, a base is added to the organic continuous phase (O phase) for neutralization, and then water (W phase) is added to perform a phase inversion from W / O to O / W, thereby dispersing the resin in the aqueous medium into particles.
[0187] The volume average particle size of the polyester resin particles dispersed in the polyester resin particle dispersion is, for example, preferably 0.01 μm to 1 μm, more preferably 0.08 μm to 0.8 μm, and further preferably 0.1 μm to 0.6 μm.
[0188] Regarding the volume average particle size of the polyester resin particles, the particle size distribution obtained by the measurement by a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by HORIBA, Ltd.) is used to draw the cumulative distribution of the volume for the particle size range (channel) divided from the small particle size side, and the particle size when the accumulation reaches 50% relative to all particles is taken as the volume average particle size D50v. In addition, the volume average particle size of particles in other dispersions is also measured in the same manner.
[0189] The content of the polyester resin particles contained in the polyester resin particle dispersion is, for example, preferably 5 mass % or more and 50 mass % or less, and more preferably 10 mass % or more and 40 mass % or less.
[0190] Similar to the polyester resin particle dispersion, a colorant dispersion and a release agent particle dispersion are also prepared. That is, the dispersion medium, dispersion method, volume average particle size of the particles, and particle content in the polyester resin particle dispersion are also the same in the colorant dispersion and the release agent particle dispersion.
[0191] ·First agglomerated particle forming step
[0192] Next, the polyester resin particle dispersion and the colorant dispersion are mixed.
[0193] Then, the polyester resin particles and the colorant particles are heterogeneously aggregated in the mixed dispersion to form first aggregated particles having a diameter close to the target diameter of the toner particles and containing the polyester resin particles and the colorant particles.
[0194] Furthermore, the first aggregated particles may contain the release agent particles by mixing the release agent particle dispersion as necessary.
[0195] Specifically, for example, a coagulant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to be acidic (for example, pH 2 or more and pH 5 or less), and after a dispersion stabilizer is added as needed, it is heated to a temperature close to the glass transition temperature of the polyester resin (specifically, for example, -30°C or more and -10°C or less of the glass transition temperature of the polyester resin) to aggregate the particles dispersed in the mixed dispersion to form first aggregated particles.
[0196] In the first agglomerated particle formation step, for example, the mixed dispersion can be stirred using a rotary shearing homogenizer, a coagulant can be added at room temperature (e.g., 25° C.), the pH of the mixed dispersion can be adjusted to acidic (e.g., pH 2 or more and pH 5 or less), a dispersion stabilizer can be added as needed, and then heating can be performed.
[0197] Examples of the coagulant include surfactants having polarity opposite to that of the surfactant contained in the mixed dispersion, inorganic metal salts, and divalent or higher metal complexes. When a metal complex is used as the coagulant, the amount of the coagulant used can be reduced, thereby improving the charging characteristics.
[0198] An additive that forms a complex or similar bond with the metal ion of the coagulant may be used together with the coagulant. As such an additive, a chelating agent may be used.
[0199] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.
[0200] As the chelating agent, a water-soluble chelating agent can be used. Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; and aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA).
[0201] The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.
[0202] · Second aggregated particle forming step
[0203] After obtaining the first aggregated particle dispersion in which the first aggregated particles are dispersed, the first aggregated particle dispersion, the polyester resin particle dispersion, and the release agent particle dispersion are further mixed. The polyester resin particle dispersion and the release agent particle dispersion may be mixed in advance and then the mixed solution may be mixed into the first aggregated particle dispersion.
[0204] Then, in the mixed dispersion in which the first aggregated particles, the polyester resin particles, and the release agent particles are dispersed, the polyester resin particles and the release agent particles are aggregated so that the polyester resin particles and the release agent particles adhere to the surfaces of the first aggregated particles, thereby forming second aggregated particles.
[0205] Specifically, for example, in the first aggregated particle forming step, when the first aggregated particles reach the target particle size, a dispersion in which polyester resin particles and release agent particles are dispersed is mixed with the first aggregated particle dispersion. Next, the mixed dispersion is heated at a temperature below the glass transition temperature of the polyester resin, the pH of the mixed dispersion is adjusted to, for example, a range of about 6.5 to 8.5, and aggregation is stopped.
[0206] Thus, second aggregated particles are obtained in which the polyester resin particles and the release agent particles are aggregated so as to adhere to the surfaces of the first aggregated particles.
[0207] Melting / combination process
[0208] Next, the second aggregated particle dispersion containing the second aggregated particles is heated, for example, to a temperature above the glass transition temperature of the polyester resin (for example, a temperature 10°C to 50°C higher than the glass transition temperature of the polyester resin) to melt / combine the second aggregated particles to form toner particles.
[0209] Through the above steps, toner particles are obtained.
[0210] In addition, the colorant particles can also be manufactured through the following steps: after obtaining the second agglomerated particle dispersion in which the second agglomerated particles are dispersed, further mixing the second agglomerated particle dispersion and the polyester resin particle dispersion in which the polyester resin particles are dispersed to agglomerate the polyester resin particles so as to further adhere to the surface of the second agglomerated particles to form third agglomerated particles; and heating the third agglomerated particle dispersion in which the third agglomerated particles are dispersed to melt / combine the third agglomerated particles to form colorant particles.
[0211] After the melting / combining step is completed, the toner particles formed in the solution are subjected to a known washing step, a solid-liquid separation step, and a drying step to obtain dry toner particles.
[0212] The washing process is not particularly limited, but from the viewpoint of chargeability, it is preferred to fully perform replacement washing with deionized water. In addition, the solid-liquid separation process is not particularly limited, but from the viewpoint of productivity, it is preferred to perform suction filtration, pressure filtration, etc. In addition, the method of the drying process is not particularly limited, but from the viewpoint of productivity, it is preferred to perform freeze drying, airflow drying, fluidized drying, vibration-type fluidized drying, etc.
[0213] The toner according to the present embodiment is produced by, for example, adding an external additive to dry toner particles and mixing them. The mixing is preferably performed by, for example, a V mixer, a Henschel mixer, a Lödige mixer, etc. Furthermore, coarse particles of the toner may be removed by using a vibration sieving machine, a wind sieving machine, etc. as needed.
[0214] - Electrostatic latent image developer -
[0215] In this embodiment, the electrostatic latent image developer contained in the developing member contains at least the above-mentioned toner. The electrostatic latent image developer may be a single-component developer containing only the toner, or a two-component developer in which the toner and a carrier are mixed.
[0216] The carrier is not particularly limited, and known carriers can be cited. Examples of the carrier include a coated carrier in which the surface of a core material containing magnetic powder is coated with a resin; a magnetic powder dispersed carrier prepared by dispersing magnetic powder in a matrix resin; and a resin impregnated carrier in which porous magnetic powder is impregnated with a resin. The magnetic powder dispersed carrier and the resin impregnated carrier can be a carrier in which the constituent particles of the carrier are used as a core material and the surface is coated with a resin.
[0217] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; and magnetic oxides such as ferrite and magnetite.
[0218] Examples of the conductive particles include particles of metals such as gold, silver, and copper; and particles of carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.
[0219] Examples of the coating resin and the matrix resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, linear silicone resin containing an organic siloxane bond or a modified product thereof, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. The coating resin and the matrix resin may contain additives such as a conductive material.
[0220] The method of coating the surface of the core material with a resin includes a method of coating with a coating layer forming solution obtained by dissolving a coating resin and various additives (used as needed) in an appropriate solvent. The solvent is not particularly limited, and can be selected by considering the type of resin used and coating suitability. Specific resin coating methods include an immersion method in which the core material is immersed in a coating layer forming solution; a spraying method in which the coating layer forming solution is sprayed on the surface of the core material; a fluidized bed method in which the coating layer forming solution is sprayed while the core material is suspended by flowing air; a kneading coating method in which the core material of the carrier and the coating layer forming solution are mixed in a kneading coater and then the solvent is removed.
[0221] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is, for example, preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.
[0222] (Cleaning scraper)
[0223] A cleaning blade used in the image forming apparatus according to the present embodiment is described. The cleaning blade is made of polyurethane resin. The total amount of F and Si present within 200 nm from the surface (contact portion) of the cleaning blade in contact with the image holder accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface.
[0224] The cleaning blade may be a single-layer blade having a single layer, a double-layer blade having an edge layer (a layer in contact with the image holding member) and a back layer, or a structure having three or more layers stacked.
[0225] -Surface ratio of F and Si-
[0226] The ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of the cleaning blade in contact with the image holder to the total amount of F and Si present within 5 μm from the surface (surface ratio of F and Si) is 75% or more. By making the surface ratio of F and Si at the contact portion of the cleaning blade 75% or more, the friction of the contact portion of the cleaning blade is reduced, the formation of toner film on the surface of the image holder can be suppressed, and the wear of the cleaning blade can be suppressed. Furthermore, the surface ratio of F and Si at the contact portion of the cleaning blade is preferably 85% or more, and more preferably 90% or more.
[0227] On the other hand, the upper limit of the surface ratio of F and Si at the contact portion of the cleaning blade is not particularly limited, but is preferably 95% or less, and more preferably 93% or less. When the surface ratio of F and Si at the contact portion of the cleaning blade is 95% or less, it is possible to suppress the occurrence of intermediate portion abutment (surface pressure drop) due to insufficient viscosity formation at the contact portion of the cleaning blade.
[0228] -Surface F and Si content-
[0229] The total amount of F and Si (surface F and Si amount) present on the surface (contact portion) of the cleaning blade in contact with the image holder is, for example, preferably 15 atm% or more, more preferably 18 atm% or more, and further preferably 20 atm% or more. When the surface F and Si amount at the contact portion of the cleaning blade is 15 atm% or more, the friction of the contact portion of the cleaning blade is reduced, the toner filming on the surface of the image holder can be suppressed, and the abrasion of the cleaning blade can be suppressed.
[0230] The upper limits of the surface F and Si content at the contact portion of the cleaning blade are not particularly limited, but are preferably 25 atm % or less, more preferably 22 atm % or less, from the viewpoint of suppressing the occurrence of defects at the contact portion of the cleaning blade.
[0231] -50nm position F and Si amount-
[0232] The total amount of F and Si present at a position 50 nm from the surface (contact portion) of the cleaning blade in contact with the image holder (the amount of F and Si at the 50 nm position) is, for example, preferably 0.3 atm% or more, more preferably 1.0 atm% or more, and further preferably 1.5 atm% or more. When the amount of F and Si at the 50 nm position of the cleaning blade is 0.3 atm% or more, the friction at the contact portion of the cleaning blade is continuously reduced, the toner filming on the surface of the image holder can be suppressed, and the time-dependent wear of the cleaning blade can also be suppressed.
[0233] The upper limits of the 50 nm position F and the Si amount of the cleaning blade are not particularly limited, but are preferably 2.0 atm % or less, and more preferably 1.8 atm % or less from the viewpoint of suppressing the occurrence of time-dependent defects at the contact portion of the cleaning blade.
[0234] The method for measuring the ratio of the total amount of F and Si present within 200 nm from the surface (contact portion) of the cleaning blade in contact with the image holder to the total amount of F and Si present within 5 μm from the surface (surface ratio of F and Si) is described. That is, the method for analyzing the amount of F and Si in the depth direction from the contact portion of the cleaning blade is described.
[0235] The area including the surface (contact portion) of the cleaning blade in contact with the image holding member was cut out, and the amounts (atm %) of each of N, C, O, F and Si elements were measured from the contact portion toward the depth direction using XPS (Versa Probe II manufactured by ULVAC-PHI, Inc.).
[0236] The total amount of F and Si present on the surface (contact portion) of the cleaning blade in contact with the image holding body was obtained by plotting the depth from the contact portion of the cleaning blade obtained by the analysis in the depth direction and the element ratio, with the area to a depth of 5 μm being SA and the area to a depth of 200 nm being SB, and the ratio being calculated according to the formula SB / SA×100. The total amount of F and Si present at a position 50 nm from the surface (contact portion) of the cleaning blade in contact with the image holding body was also obtained in the same manner.
[0237] -100% modulus (M100)-
[0238] The 100% modulus at 23° C. of the surface (contact portion) of the cleaning blade in contact with the image holder is preferably 11 MPa or more and 22 MPa or less. Hereinafter, the 100% modulus at 23° C. of the contact portion of the cleaning blade is also referred to as “M100”.
[0239] When M100 is 11 MPa or more, streak-like image defects caused by partial lifting of the squeegee are suppressed. From the viewpoint of suppressing streak-like image defects caused by partial lifting of the squeegee, M100 is, for example, more preferably 13 MPa or more, and further preferably 15 MPa or more.
[0240] Furthermore, when M100 is 22 MPa or less, toner filming on the image holding member is suppressed. From the viewpoint of suppressing toner filming, M100 is, for example, more preferably 20 MPa or less, and further preferably 18 MPa or less.
[0241] The M100 is a value obtained from the stress at 100% deformation at 23°C using a dumbbell No. 3 test piece at a tensile speed of 500 mm / min in accordance with JIS K6251 (2010). The measuring device used is, for example, STROGRAPH AE elastomer manufactured by TOYOSEIKI KOGYO CO. LTD.
[0242] As a method for setting the above-mentioned M100 within the above-mentioned range, there can be cited a method of adjusting the composition of the base material of the cleaning blade, etc. Specifically, there can be cited a method of adjusting the content of the polyisocyanate component when the base material contains polyurethane rubber, a method of selecting at least one of the type and addition amount of the cross-linking agent when a cross-linking agent is used in the manufacture of the base material, and a combination thereof, etc. In addition, if the content of the polyisocyanate component is increased, M100 increases.
[0243] -structure-
[0244] The cleaning blade is made of polyurethane resin.
[0245] Polyurethane resin
[0246] The polyurethane resin is a polyurethane resin obtained by polymerizing at least a polyol component and a polyisocyanate component. The polyurethane resin may be a polyurethane resin obtained by polymerizing a resin having a functional group that can react with an isocyanate group of a polyisocyanate in addition to the polyol component as needed.
[0247] For example, the polyurethane resin preferably has a hard segment and a soft segment. The "hard segment" and the "soft segment" refer to segments in which the material constituting the former is composed of a relatively harder material than the material constituting the latter, and the material constituting the latter is composed of a relatively softer material than the material constituting the former.
[0248] In addition, as the material constituting the hard segment (hard segment material), there can be mentioned a low molecular weight polyol component among the polyol components, a resin having a functional group capable of reacting with an isocyanate group of a polyisocyanate, etc. On the other hand, as the material constituting the soft segment (soft segment material), there can be mentioned a high molecular weight polyol component among the polyol components.
[0249] Here, the average particle size of the aggregates of the hard segments is, for example, preferably 1 μm or more and 10 μm or less, and more preferably 1 μm or more and 5 μm or less.
[0250] By setting the average particle size of the hard segment aggregates to 1 μm or more, the frictional resistance on the contact member surface is easily reduced. Therefore, the blade behavior becomes stable and local wear is easily suppressed.
[0251] On the other hand, by setting the average particle size of the hard segment aggregates to 10 μm or less, the occurrence of chipping can be easily suppressed.
[0252] The average particle size of the hard segment aggregates was measured as follows: an image was captured at a magnification of ×20 using a polarizing microscope (BX51-P manufactured by Olympus Corporation), the image was processed to binarize the image, 5 points were measured on each cleaning blade (the particle size of 5 aggregates was measured at each point), the particle size (equivalent circle diameter) of the aggregates was measured for 20 cleaning blades, and the average particle size was calculated from a total of 500.
[0253] The image was binarized using image processing software OLYMPUS Stream essentials (manufactured by Olympus Corporation) to adjust the thresholds of hue / chroma / brightness so that the crystal part and the hard segment aggregates were black and the amorphous part (equivalent to the soft segment) was white.
[0254] Polyol ingredients
[0255] The polyol component includes high molecular weight polyols and low molecular weight polyols.
[0256] The high molecular weight polyol component is a polyol having a number average molecular weight of 500 or more (e.g., preferably 500 or more and 5000 or less). As the high molecular weight polyol component, polyester polyols obtained by dehydration condensation of low molecular weight polyols and dibasic acids, polycarbonate polyols obtained by reaction of low molecular weight polyols and alkyl carbonates, polycaprolactone polyols, polyether polyols and other well-known polyols can be cited. In addition, as commercially available products of high molecular weight polyols, for example, PLAXEL205 or PLAXEL240 manufactured by Daicel Corporation can be cited.
[0257] Here, the number average molecular weight is a value measured by gel permeation chromatography (GPC). The same shall apply hereinafter.
[0258] These high molecular weight polyols may be used alone or in combination of two or more.
[0259] The polymerization ratio of the high molecular weight polyol component is preferably, for example, 30 mol % or more and 50 mol % or less, and preferably 40 mol % or more and 50 mol % or less, based on all the polymerization components of the polyurethane resin.
[0260] The low-molecular-weight polyol component is a polyol having a molecular weight (number average molecular weight) of less than 500. The low-molecular-weight polyol is a material that functions as a chain extender and a cross-linking agent.
[0261] Examples of the low molecular weight polyol component include 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,20-eicosandiol. Among them, 1,4-butanediol is preferably used as the low molecular weight polyol component.
[0262] Examples of the low molecular weight polyol component include diol (bifunctional), triol (trifunctional) and tetraol (tetrafunctional) which are well known as chain extenders and crosslinking agents.
[0263] These polyols may be used alone or in combination of two or more.
[0264] The polymerization ratio of the low molecular weight polyol relative to all the polymerization components of the polyurethane resin is preferably greater than 50 mol% and less than 75 mol%, preferably greater than 52 mol% and less than 75 mol%, more preferably greater than 55 mol% and less than 75 mol%, and further preferably greater than 55 mol% and less than 60 mol%.
[0265] Polyisocyanate ingredients
[0266] Examples of the polyisocyanate component include 4,4-diphenylmethane diisocyanate (MDI), 2,6-toluene diisocyanate (TDI), 1,6-hexane diisocyanate (HDI), 1,5-naphthalene diisocyanate (NDI), and 3,3′-dimethylbiphenyl-4,4′-diisocyanate (TODI).
[0267] As the polyisocyanate component, for example, 4,4′-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate (NDI), and hexamethylene diisocyanate (HDI) are more preferable.
[0268] These polyisocyanate components may be used alone or in combination of two or more.
[0269] The polymerization ratio of the polyisocyanate component is preferably, for example, 5 mol % or more and 25 mol % or less, and preferably 10 mol % or more and 20 mol % or less, based on all the polymerization components of the polyurethane resin.
[0270] Resins having functional groups capable of reacting with isocyanate groups
[0271] The resin having a functional group capable of reacting with an isocyanate group (hereinafter referred to as "functional group-containing resin") is preferably a flexible resin, and from the viewpoint of flexibility, an aliphatic resin having a linear structure is more preferred. Specific examples of the functional group-containing resin include acrylic resins containing two or more hydroxyl groups, polybutadiene resins containing two or more hydroxyl groups, and epoxy resins having two or more epoxy groups.
[0272] Examples of commercially available products of acrylic resins containing two or more hydroxyl groups include ACTFLOW manufactured by Soken Chemical & Engineering Co., Ltd. (grades: UMB-2005B, UMB-2005P, UMB-2005, UME-2005, etc.).
[0273] Examples of commercially available products of the polybutadiene resin containing two or more hydroxyl groups include R-45HT manufactured by IDEMITSU LUBE.
[0274] As the epoxy resin having two or more epoxy groups, for example, an epoxy resin having a hard and brittle property as conventional general epoxy resins is not preferred, and an epoxy resin having a softer and tougher property than conventional epoxy resins is preferred. As the above-mentioned epoxy resin, for example, from the viewpoint of molecular structure, an epoxy resin having a structure (flexible skeleton) capable of improving the mobility of the main chain in its main chain structure is preferred, and as the flexible skeleton, for example, an alkylene skeleton, a cycloalkane skeleton, a polyoxyalkylene skeleton, etc. can be cited, and a polyoxyalkylene skeleton is particularly preferred.
[0275] Furthermore, from the viewpoint of physical properties, epoxy resins having a lower viscosity than the molecular weight are preferred compared to conventional epoxy resins. Specifically, for example, the weight average molecular weight is preferably within the range of 900±100, and the viscosity at 25°C is preferably within the range of 15000±5000 mPa·s, more preferably within the range of 15000±3000 mPa·s. Commercially available epoxy resins having such properties include, for example, EPICLON EX A-4850-150 manufactured by DIC CORPORATION.
[0276] The polymerization ratio of the functional group-containing resin is preferably set within a range that does not impair the characteristics of the cleaning blade, for example.
[0277] ·Production method of polyurethane resin
[0278] The polyurethane resin can be produced by a conventional polyurethane production method such as a prepolymer method or a one-shot method. The prepolymer method is suitable for this embodiment because it can produce polyurethane with excellent wear resistance and chipping resistance, but the method is not limited thereto.
[0279] The cleaning blade is produced by forming the cleaning blade-forming composition prepared by the above method into a sheet by centrifugal molding, extrusion molding, or the like, and then cutting the sheet.
[0280] Here, examples of the catalyst used in the production of the polyurethane resin include amine compounds such as tertiary amines, organic metal compounds such as quaternary ammonium salts and organic tin compounds, and the like.
[0281] Examples of the tertiary amine include trialkylamines such as triethylamine, tetraalkyldiamines such as N,N,N',N'-tetramethyl-1,3-butanediamine, amino alcohols such as dimethylethanolamine, ethoxylated amines, ethoxylated diamines, esteramines such as bis(diethylethanolamine) adipate, triethylenediamine (TEDA), cyclohexylamine derivatives such as N,N-dimethylcyclohexylamine, morpholine derivatives such as N-methylmorpholine and N-(2-hydroxypropyl)-dimethylmorpholine, piperazine derivatives such as N,N'-diethyl-2-methylpiperazine and N,N'-bis-(2-hydroxypropyl)-2-methylpiperazine, and the like.
[0282] Examples of the quaternary ammonium salt include 2-hydroxypropyltrimethylammonium-octylate, 1,5-diazabicyclo[4.3.0]nonene-5(DBN)-octylate, 1,8-diazabicyclo[5.4.0]undecene-7(DBU)-octylate, DBU-oleate, DBU-p-toluenesulfonate, DBU-formatate, and 2-hydroxypropyltrimethylammonium-formatate.
[0283] Examples of the organic tin compound include dialkyltin compounds such as dibutyltin dilaurate and dibutyltin di(2-ethylhexanoate), stannous 2-ethylhexanoate, and stannous oleate.
[0284] Among these catalysts, triethylenediamine (TEDA) which is a tertiary ammonium salt is used from the viewpoint of hydrolysis resistance, and quaternary ammonium salts are used from the viewpoint of processability. Among the quaternary ammonium salts, 1,5-diazabicyclo[4.3.0]nonene-5(DBN)-octanoate, 1,8-diazabicyclo[5.4.0]undecene-7(DBU)-octanoate, and DBU-formate which have high reactivity are used.
[0285] The content of the catalyst is, for example, preferably in the range of 0.0005% by mass or more and 0.03% by mass or less, and particularly preferably 0.001% by mass or more and 0.01% by mass or less, based on the entire polyurethane resin constituting the contact member.
[0286] These are used alone or in combination of two or more.
[0287] ·Manufacturing of double-layer cleaning scraper
[0288] For example, when the cleaning blade has a two-layer structure of an edge layer and a back layer, the cleaning blade is produced by separately producing the edge layer and the back layer by the above-mentioned method for producing a polyurethane resin and bonding the obtained edge layer and back layer together.
[0289] When making the hardness of the edge layer and the back layer different from each other, a method of changing the material of the polyurethane resin can be mentioned, for example, a method of changing the ratio of the hard segment to the soft block can be mentioned.
[0290] Modification of contact parts
[0291] In this embodiment, since the ratio of the total amount of F and Si present within 200nm from the surface (contact portion) of the cleaning scraper in contact with the image holder to the total amount of F and Si present within 5μm from the surface (surface ratio of F and Si) is set within the above-mentioned range, it is preferred to allow at least one of the F element and the Si element to penetrate into the contact portion of the obtained cleaning scraper, thereby having a modified layer that has been subjected to surface modification treatment.
[0292] The modified layer is a layer obtained by impregnating a surface treatment liquid containing an isocyanate compound, a specific polymer having at least one of F element and Si element, and an organic solvent into the contact portion of the cleaning blade and curing the surface treatment liquid (ie, the isocyanate compound and the specific polymer).
[0293] The modified layer is formed integrally with the surface layer of the contact portion so as to gradually become sparse from the surface toward the inside.
[0294] Examples of the isocyanate compound include 2,6-toluene diisocyanate (TDI), 4,4'-diphenylmethane diisocyanate (MDI), p-phenylene diisocyanate (PPDI), 1,5-naphthalene diisocyanate (NDI), 3,3'-dimethylbiphenyl-4,4'-diisocyanate (TODI), and polymers thereof and modified products thereof. In addition, examples of modified products of the isocyanate compound include urethane prepolymers obtained by prepolymerizing an isocyanate compound with a polyol.
[0295] The specific polymer is preferably a compound that reacts with an isocyanate compound and chemically bonds thereto. Examples of acrylic polymers having a siloxane bond include block copolymers of (meth)acrylate and (meth)siloxane acrylate and derivatives thereof. In addition, "(meth)acrylic acid" means either or both of acrylic acid and methacrylic acid.
[0296] Examples of the acrylic polymer having a fluorine atom include a block copolymer of (meth)acrylic acid ester and fluoroalkyl methacrylate and a derivative thereof.
[0297] For example, the cleaning blade preferably contains a polymer having a siloxane bond (silicone-based polymer) in a portion in contact with the image holding member.
[0298] Furthermore, from the viewpoint of solubility in an organic solvent, the specific polymer is preferably a compound having a hydroxyl group, an alkyl group, or a carboxyl group, for example.
[0299] In addition, as a method for confirming that the surface layer of the contact portion of the cleaning blade contains a specific polymer and a method for confirming that the surface layer contains a specific polymer that is an acrylic polymer, for example, the following method can be cited. Specifically, the confirmation is as follows: the structure estimation or composition analysis of the surface layer material of the contact portion of the cleaning blade is performed by an analysis method such as Fourier transform infrared spectrophotometer (FTIR) or X-ray photoelectron spectroscopy (XPS).
[0300] The content of the specific polymer in the surface treatment liquid is, for example, 8 parts by mass to 13 parts by mass, preferably 9 parts by mass to 13 parts by mass, and more preferably 10 parts by mass to 13 parts by mass, relative to 100 parts by mass of the isocyanate compound.
[0301] The organic solvent is preferably a solvent that dissolves the specific polymer and is compatible with the isocyanate compound, and specifically includes ethyl acetate, methyl ethyl ketone (MEK), toluene, acetone, cyclohexanone, etc. In addition, as the organic solvent, a reactive diluent such as 2-hydroxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-hydroxyethyl methacrylate, hydroxypropyl methacrylate, glycidyl methacrylate, neopentyl glycol diacrylate, hexanediol diacrylate, trimethylolpropane triacrylate, etc. can be used.
[0302] The modified layer is formed, for example, by impregnating and applying the surface treatment liquid to at least the contact portion of the cleaning blade, removing the organic solvent by drying, and forming a cured layer by heat treatment.
[0303] The impregnation coating method is not particularly limited, and examples thereof include common methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, curtain coating, etc. When the impregnation coating method is the impregnation coating method, the impregnation time may be, for example, in the range of 10 seconds to 60 seconds.
[0304] Drying conditions after impregnation coating include, for example, a temperature of 20° C. to 30° C. and a time of 1 minute to 10 minutes. Heat treatment conditions include, for example, a temperature of 50° C. to 80° C. and a time of 60 minutes to 90 minutes.
[0305] Pressing force NF, pressing angle WA
[0306] The product of the static pressing force NF and the pressing angle WA between the cleaning blade and the image holder (NF×WA) is preferably, for example, 40 or more and 60 or less. When NF×WA is 40 or more, the toner leakage at the contact position between the image holder and the cleaning blade can be suppressed. On the other hand, when NF×WA is 60 or less, the toner filming on the surface of the image holder can be further suppressed. NF×WA is more preferably 45 or more and 58 or less, and further preferably 50 or more and 56 or less.
[0307] The pressing force NF of the cleaning blade is calculated by the following formula.
[0308] Formula: Pressing force NF = k × d
[0309] Wherein, k represents the spring constant inherent to the cleaning blade, and d represents the amount of penetration of the cleaning blade relative to the image holder (reference Figure 4 ).
[0310] The spring constant k inherent to the cleaning blade is obtained by displacing the cleaning blade 12 and measuring the load with a load cell.
[0311] Regarding the amount d of the cleaning blade biting into the image support, the cleaning blade 12 was fixed to a supporting member and the displacement amount of the cleaning blade when the cleaning blade was brought into contact with the image support was calculated.
[0312] In addition, regarding the pressing angle WA of the cleaning scraper relative to the image holder, the pressing angle WA is calculated by the following formula using the free length L of the cleaning scraper CB (the length of the portion not fixed by the supporting component CBC) and the set angle θ of the cleaning scraper CB (i.e., the angle formed at the contact point between the straight portion of the cleaning scraper CB (the portion not bent due to pressing on the image holder BE) and the image holder BE).
[0313] Formula: Pressing angle WA = θ-tan -1 (3d / 2L)
[0314] Here, in Figure 4 In the figure, BE represents an image holding body, CB represents a cleaning blade, and CBS represents a supporting member that supports the cleaning blade.
[0315] The static pressing force NF (Normal Force) of the cleaning blade against the image holding member is, for example, preferably 1.5 gf / mm or more and 3.5 gf / mm or less, and more preferably 2.3 gf / mm or more and 3.2 gf / mm or less.
[0316] The amount d of the cleaning blade biting into the image holding member is, for example, preferably from 0 mm to 10 mm, and more preferably from 0.01 mm to 5 mm.
[0317] (Image holding body)
[0318] An image holder used in the image forming apparatus according to the present embodiment will be described. In the present embodiment, an electrophotographic photoreceptor (hereinafter also referred to as a "photoreceptor") is used as an image holder having a toner image formed on its surface.
[0319] Examples of the photoreceptor include a photoreceptor having a conductive substrate and a photosensitive layer provided on the conductive substrate.
[0320] Hereinafter, the electrophotographic photoreceptor will be described with reference to the drawings.
[0321] Figure 1 The electrophotographic photoreceptor 7 shown may have a structure in which an undercoat layer 1, a charge generating layer 2, and a charge transporting layer 3 are sequentially stacked on a conductive support 4. The charge generating layer 2 and the charge transporting layer 3 constitute a photosensitive layer 5.
[0322] The electrophotographic photoreceptor 7 may have a layer structure without the undercoat layer 1 .
[0323] Furthermore, the electrophotographic photoreceptor 7 may be a photoreceptor having a single-layer photosensitive layer integrating the functions of the charge generating layer 2 and the charge transporting layer 3. In the case of a photoreceptor having a single-layer photosensitive layer, the single-layer photosensitive layer constitutes the outermost layer.
[0324] Furthermore, the electrophotographic photoreceptor 7 may be a photoreceptor having a surface protective layer on the charge transport layer 3 or on the single-layer photosensitive layer. In the case of a photoreceptor having a surface protective layer, the surface protective layer constitutes the outermost layer.
[0325] Hereinafter, each layer of the electrophotographic photoreceptor will be described in detail, and reference numerals will be omitted in the description.
[0326] (Conductive substrate)
[0327] As the conductive substrate, for example, metal plates, metal drums and metal belts containing metals (aluminum, copper, zinc, chromium, nickel, molybdenum, vanadium, indium, gold, platinum, etc.) or alloys (stainless steel, etc.) can be cited. In addition, as the conductive substrate, for example, paper, resin films, belts, etc. formed by coating, vapor deposition or lamination of conductive compounds (for example, conductive polymers, indium oxide, etc.), metals (for example, aluminum, palladium, gold, etc.) or alloys can also be cited. Here, "conductive" means that the volume resistivity is less than 10 13 Ω·cm.
[0328] When the electrophotographic photoreceptor is used in a laser printer, the surface of the conductive substrate is preferably roughened to 0.04 μm or more and 0.5 μm or less in terms of center line average roughness Ra for the purpose of suppressing interference fringes generated when irradiating a laser beam. In addition, when non-interference light is used as a light source, it is not particularly necessary to prevent the roughening of interference fringes, but since defects caused by the unevenness of the conductive substrate surface are suppressed, it is suitable for further extending the life.
[0329] Examples of the roughening method include wet grinding in which an abrasive is suspended in water and sprayed onto the conductive substrate, centerless grinding in which the conductive substrate is pressed against a rotating grinding wheel and continuously ground, and anodizing.
[0330] As a roughening method, there is also a method in which a conductive or semiconductive powder is dispersed in a resin without roughening the surface of the conductive substrate to form a layer on the surface of the conductive substrate, and roughening is performed using particles dispersed in the layer.
[0331] The roughening treatment based on anodization is a process of forming an oxide film on the surface of a conductive substrate by anodizing a metal (e.g., aluminum) conductive substrate as an anode in an electrolyte solution. As an electrolyte solution, for example, sulfuric acid solution, oxalic acid solution, etc. can be cited. However, the porous anodized film formed by anodization is chemically active in this state, easily contaminated, and the resistance change caused by the environment is also large. Therefore, for example, it is preferred that the porous anodized film is used in pressurized steam or boiling water (metal salts such as nickel can be added) to block the micropores of the oxide film using the volume expansion caused by water and reaction to change to a more stable hydrated oxide sealing treatment.
[0332] The film thickness of the anodic oxide film is preferably, for example, 0.3 μm or more and 15 μm or less. When the film thickness is within the above range, the barrier property against injection tends to be exhibited, and the increase in residual potential due to repeated use tends to be suppressed.
[0333] The conductive substrate may be subjected to a treatment using an acidic treatment liquid or a boehmite treatment.
[0334] The treatment based on the acidic treatment solution is carried out, for example, as follows. First, an acidic treatment solution containing phosphoric acid, chromic acid and hydrofluoric acid is prepared. The blending ratio of phosphoric acid, chromic acid and hydrofluoric acid in the acidic treatment solution is preferably, for example, in the range of 10 mass % to 11 mass % for phosphoric acid, in the range of 3 mass % to 5 mass % for chromic acid, in the range of 0.5 mass % to 2 mass % for hydrofluoric acid, and the overall concentration of these acids is in the range of 13.5 mass % to 18 mass %. The treatment temperature is, for example, preferably 42° C. to 48° C. The film thickness of the coating is, for example, preferably 0.3 μm to 15 μm.
[0335] The boehmite treatment is performed, for example, by immersing in pure water at 90°C to 100°C for 5 to 60 minutes or contacting with heated steam at 90°C to 120°C for 5 to 60 minutes. The film thickness of the coating is preferably 0.1 μm to 5 μm. An anodizing treatment can be performed using an electrolyte solution with low coating solubility such as adipic acid, boric acid, borate, phosphate, phthalate, maleate, benzoate, tartrate, or citrate.
[0336] (lower coating)
[0337] The undercoat layer is, for example, a layer containing inorganic particles and a binder resin.
[0338] Examples of inorganic particles include particles having a powder resistance (volume resistivity) of 10 2 Ω·cm or more and 10 11 Inorganic particles with a particle size of less than Ω·cm.
[0339] Among them, as the inorganic particles having the above resistance value, metal oxide particles such as tin oxide particles, titanium oxide particles, zinc oxide particles, and zirconium oxide particles are preferred, and zinc oxide particles are particularly preferred.
[0340] The specific surface area of the inorganic particles based on the BET method is preferably 10 m 2 / g or above.
[0341] The volume average particle diameter of the inorganic particles is, for example, preferably 50 nm or more and 2000 nm or less (for example, more preferably 60 nm or more and 1000 nm or less).
[0342] The content of the inorganic particles is, for example, preferably 10% by mass or more and 80% by mass or less, and more preferably 40% by mass or more and 80% by mass or less, based on the binder resin.
[0343] The inorganic particles may be subjected to a surface treatment. Two or more inorganic particles having different surface treatments or different particle sizes may be mixed and used.
[0344] Examples of the surface treatment agent include silane coupling agents, titanate coupling agents, aluminum coupling agents, surfactants, etc. In particular, for example, a silane coupling agent is preferred, and a silane coupling agent having an amino group is more preferred.
[0345] Examples of the silane coupling agent having an amino group include, but are not limited to, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, and N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane.
[0346] Silane coupling agents can be mixed with two or more for use. For example, silane coupling agents having amino groups and other silane coupling agents can be used simultaneously. As other silane coupling agents, for example, vinyl trimethoxysilane, 3-methacryloxypropyl-tris (2-methoxyethoxy) silane, 2- (3,4-epoxycyclohexyl) ethyl trimethoxysilane, 3-glycidoxypropyl trimethoxysilane, vinyl triacetoxysilane, 3-mercaptopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, N-2- (aminoethyl) -3-aminopropyl trimethoxysilane, N-2- (aminoethyl) -3-aminopropyl methyl dimethoxysilane, N, N-bis (2-hydroxyethyl) -3-aminopropyl triethoxysilane, 3-chloropropyl trimethoxysilane, etc. can be cited, but it is not limited thereto.
[0347] The surface treatment method using the surface treatment agent may be any method as long as it is a known method, and may be either a dry method or a wet method.
[0348] The treatment amount of the surface treatment agent is preferably, for example, 0.5 mass % or more and 10 mass % or less relative to the inorganic particles.
[0349] Here, from the viewpoint of improving the long-term stability of electrical characteristics and carrier blocking properties, the undercoat layer preferably contains an electron accepting compound (acceptor compound) together with inorganic particles, for example.
[0350] As electron-accepting compounds, for example, there can be mentioned quinone compounds such as chloranil and tetrabromobenzoquinone; tetracyanobenzoquinone dimethane compounds; fluorenone compounds such as 2,4,7-trinitrofluorenone and 2,4,5,7-tetranitro-9-fluorenone; oxadiazole compounds such as 2-(4-biphenyl)-5-(4-tert-butylphenyl)-1,3,4-oxadiazole, 2,5-bis(4-naphthyl)-1,3,4-oxadiazole, and 2,5-bis(4-diethylaminophenyl)-1,3,4-oxadiazole; xanthone compounds; thiophene compounds; electron-transporting substances such as diphenylquinone compounds such as 3,3',5,5'-tetra-tert-butyldiphenylquinone, and the like.
[0351] In particular, as the electron accepting compound, for example, a compound having an anthraquinone structure is preferred. As the compound having an anthraquinone structure, for example, hydroxyanthraquinone compounds, aminoanthraquinone compounds, aminohydroxyanthraquinone compounds, etc. are preferred, and specifically, for example, anthraquinone, alizarin, quinizarin, anthraquinone, purpurin, etc. are preferred.
[0352] The electron accepting compound may be contained in the undercoat layer in a dispersed state together with the inorganic particles, or may be contained in a state of being attached to the surface of the inorganic particles.
[0353] Examples of a method for attaching the electron accepting compound to the surface of the inorganic particles include a dry method and a wet method.
[0354] The dry method is, for example, a method in which an electron accepting compound is directly added dropwise or dissolved in an organic solvent and sprayed together with dry air or nitrogen to attach the electron accepting compound to the surface of the inorganic particles while stirring the inorganic particles with a mixer having a large shear force. When the electron accepting compound is added dropwise or sprayed, it is preferably carried out at a temperature below the boiling point of the solvent. After the electron accepting compound is added dropwise or sprayed, calcination can be further carried out under conditions of more than 100°C. As long as the temperature and time at which the electrophotographic properties can be obtained are not particularly limited.
[0355] The wet method is, for example, the following method: while dispersing the inorganic particles in a solvent by stirring, ultrasonic waves, a sand mill, a grinder, a ball mill, etc., an electron accepting compound is added, and after stirring or dispersing, the solvent is removed to attach the electron accepting compound to the surface of the inorganic particles. The solvent removal method is, for example, to remove the solvent by filtering or distilling. After removing the solvent, calcination can be further performed at a condition of more than 100°C. As long as the temperature and time are such that the electronic photographic characteristics can be obtained, the calcination is not particularly limited. In the wet method, the water content of the inorganic particles can be removed before adding the electron accepting compound. As examples thereof, a method of removing the water content while stirring and heating in a solvent and a method of removing the water content by azeotropy with the solvent can be cited.
[0356] The electron accepting compound may be attached before or after the inorganic particles are surface treated with a surface treatment agent, or the electron accepting compound may be attached and the surface treated with a surface treatment agent may be simultaneously performed.
[0357] The content of the electron accepting compound is, for example, preferably 0.01 mass % to 20 mass %, and preferably 0.01 mass % to 10 mass %, based on the inorganic particles.
[0358] Examples of the binder resin used in the undercoat layer include acetal resins (e.g., polyvinyl butyral), polyvinyl alcohol resins, polyvinyl acetal resins, casein resins, polyamide resins, cellulose resins, gelatin, polyurethane resins, polyester resins, unsaturated polyester resins, methacrylic resins, acrylic resins, polyvinyl chloride resins, polyvinyl acetate resins, vinyl chloride-vinyl acetate-maleic anhydride resins, silicone resins, silicone-alkyd resins, urea resins, phenolic resins, phenol-formaldehyde resins, melamine resins, urethane resins, alkyd resins, epoxy resins and other well-known polymer compounds; zirconium chelate compounds; titanium chelate compounds; aluminum chelate compounds; titanium alkoxide compounds; organic titanium compounds; silane coupling agents and other well-known materials.
[0359] Examples of the binder resin used in the undercoat layer include a charge transporting resin having a charge transporting group, and a conductive resin (eg, polyaniline).
[0360] Among them, as the binding resin used in the lower coating layer, for example, a resin that is insoluble in the coating solvent in the upper layer is preferred, and particularly preferably a resin obtained by the reaction between a curing agent and at least one resin selected from the group consisting of thermosetting resins such as urea resin, phenolic resin, phenol-formaldehyde resin, melamine resin, urethane resin, unsaturated polyester resin, alkyd resin, epoxy resin, polyamide resin, polyester resin, polyether resin, methacrylic resin, acrylic resin, polyvinyl alcohol resin and polyvinyl acetal resin.
[0361] When two or more of these binder resins are used in combination, the mixing ratio thereof is set as necessary.
[0362] The undercoat layer may contain various additives to improve electrical characteristics, environmental stability and image quality.
[0363] As additives, there can be mentioned known materials such as polycyclic condensed system, azo system, etc., electron transporting pigments, zirconium chelate compounds, titanium chelate compounds, aluminum chelate compounds, titanium alkoxide compounds, organic titanium compounds, silane coupling agents, etc. As mentioned above, silane coupling agents are used for surface treatment of inorganic particles, but can also be further added to the undercoat layer as an additive.
[0364] Examples of the silane coupling agent as an additive include vinyltrimethoxysilane, 3-methacryloxypropyl-tri(2-methoxyethoxy)silane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, vinyltriacetoxysilane, 3-mercaptopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N,N-bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, and 3-chloropropyltrimethoxysilane.
[0365] Examples of the zirconium chelate compound include zirconium butoxide, zirconium ethyl acetoacetate, zirconium triethanolamine, zirconium acetylacetonate butoxide, zirconium ethyl acetoacetate butoxide, zirconium acetate, zirconium oxalate, zirconium lactate, zirconium phosphonate, zirconium octanoate, zirconium naphthenate, zirconium laurate, zirconium stearate, zirconium isostearate, zirconium methacrylate butoxide, zirconium stearate butoxide, and zirconium isostearate butoxide.
[0366] Examples of the titanium chelate compound include tetraisopropyl titanate, tetra-n-butyl titanate, butyl titanate dimer, tetra(2-ethylhexyl) titanate, titanium acetylacetonate, titanium polyacetylacetonate, titanium octanediol, ammonium lactate titanium, titanium lactate, ethyl titanium lactate, triethanolamine titanium, and polyhydroxystearate titanium.
[0367] Examples of the aluminum chelate compound include aluminum isopropoxide, monobutoxyaluminum diisopropoxide, aluminum butoxide, diethyl acetoacetate aluminum diisopropoxide, and tris(ethyl acetoacetate)aluminum.
[0368] These additives may be used alone or as a mixture or polycondensate of plural compounds.
[0369] The undercoat layer preferably has a Vickers hardness of 35 or more, for example.
[0370] In order to suppress interference fringe images, the surface roughness (ten-point average roughness) of the undercoat layer is preferably adjusted to, for example, 1 / (4n) (n is the refractive index of the upper layer) to 1 / 2 of the wavelength λ of the exposure laser used.
[0371] In order to adjust the surface roughness, resin particles or the like may be added to the undercoat layer. Examples of the resin particles include silicone resin particles and cross-linked polymethyl methacrylate resin particles. In addition, in order to adjust the surface roughness, the surface of the undercoat layer may be ground. Examples of the grinding method include polishing, sandblasting, wet grinding, grinding, and the like.
[0372] The formation of the undercoat layer is not particularly limited and can be performed by a known formation method. For example, a coating film of an undercoat layer-forming coating liquid obtained by adding the above components to a solvent is formed, and the coating film is dried and, if necessary, heated.
[0373] Examples of the solvent used for preparing the coating solution for forming an undercoat layer include known organic solvents such as alcohol solvents, aromatic hydrocarbon solvents, halogenated hydrocarbon solvents, ketone solvents, ketone alcohol solvents, ether solvents, and ester solvents.
[0374] Specific examples of these solvents include common organic solvents such as methanol, ethanol, n-propanol, isopropanol, n-butanol, benzyl alcohol, methyl cellosolve, ethyl cellosolve, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, ethyl acetate, n-butyl acetate, dioxane, tetrahydrofuran, dichloromethane, chloroform, chlorobenzene, and toluene.
[0375] Examples of a method for dispersing the inorganic particles when preparing the coating liquid for forming an undercoat layer include known methods such as a roll mill, a ball mill, a vibration ball mill, an attritor, a sand mill, a colloid mill, and a paint shaker.
[0376] Examples of a method for applying the coating liquid for forming an undercoat layer onto the conductive substrate include common methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, and curtain coating.
[0377] The film thickness of the undercoat layer is preferably set to, for example, 15 μm or more, and more preferably set to within the range of 20 μm or more and 50 μm or less.
[0378] (Middle layer)
[0379] Although not shown in the figure, an intermediate layer may be further provided between the undercoat layer and the photosensitive layer.
[0380] The intermediate layer is, for example, a layer containing a resin. Examples of the resin used for the intermediate layer include acetal resins (e.g., polyvinyl butyral, etc.), polyvinyl alcohol resins, polyvinyl acetal resins, casein resins, polyamide resins, cellulose resins, gelatin, polyurethane resins, polyester resins, methacrylic resins, acrylic resins, polyvinyl chloride resins, polyvinyl acetate resins, vinyl chloride-vinyl acetate-maleic anhydride resins, silicone resins, silicone-alkyd resins, phenol-formaldehyde resins, melamine resins and other polymer compounds.
[0381] The intermediate layer may be a layer containing an organic metal compound. Examples of the organic metal compound used for the intermediate layer include organic metal compounds containing metal atoms such as zirconium, titanium, aluminum, manganese, and silicon.
[0382] These compounds for the intermediate layer may be used alone or as a mixture or polycondensate of plural compounds.
[0383] Among them, the intermediate layer is preferably a layer containing an organic metal compound containing zirconium atoms or silicon atoms, for example.
[0384] The formation of the intermediate layer is not particularly limited and can be performed by a known formation method. For example, a coating film of an intermediate layer-forming coating liquid obtained by adding the above components to a solvent is formed, and the coating film is dried and, if necessary, heated.
[0385] As a coating method for forming the intermediate layer, a common method such as a dip coating method, a push coating method, a wire bar coating method, a spray coating method, a blade coating method, an air knife coating method, a curtain coating method, etc. can be used.
[0386] The film thickness of the intermediate layer is preferably set within a range of, for example, 0.1 μm or more and 3 μm or less.
[0387] (Charge Generation Layer)
[0388] The charge generating layer is, for example, a layer containing a charge generating material and a binder resin. Furthermore, the charge generating layer may also be a vapor-deposited layer of the charge generating material. The vapor-deposited layer of the charge generating material is suitable for the case where a non-interference light source such as an LED (Light Emitting Diode) or an organic EL (Electro-luminescence) image array is used.
[0389] Examples of the charge generating material include azo pigments such as disazo and trisazo; condensed ring aromatic pigments such as dibromoanthraquinone; perylene pigments; pyrrolopyrrole pigments; phthalocyanine pigments; zinc oxide; and trigonal selenium.
[0390] Among them, in order to cope with laser exposure in the near-infrared region, metal phthalocyanine pigments or metal-free phthalocyanine pigments are preferably used as charge generating materials, and more specifically, hydroxygallium phthalocyanine, chlorogallium phthalocyanine, dichlorotin phthalocyanine, and oxytitanium phthalocyanine are more preferred.
[0391] On the other hand, in order to cope with laser exposure in the near-ultraviolet region, preferred charge generating materials include condensed ring aromatic pigments such as dibromoanthraquinone, thioindigo pigments, porphyrazine compounds, zinc oxide, trigonal selenium, and disazo pigments.
[0392] Even when using a non-interference light source such as an LED or an organic EL image array whose central wavelength of light emission is within the range of 450nm to 780nm, the above-mentioned charge generating material can be used. However, from the viewpoint of resolution, when a photosensitive layer is used as a thin film of 20μm or less, the electric field intensity in the photosensitive layer increases, and the charge injection from the substrate causes a drop in charge, so-called image defects called black spots. This becomes significant when using a charge generating material that easily generates dark current in a p-type semiconductor such as trigonal selenium or phthalocyanine pigment.
[0393] On the other hand, when n-type semiconductors such as condensed ring aromatic pigments, perylene pigments, and azo pigments are used as charge generating materials, dark current is less likely to be generated, and image defects called black spots can be suppressed even when thin films are used.
[0394] The n-type is determined by the polarity of the photocurrent flowing by the commonly used time-of-flight method, and the one in which electrons flow more easily as carriers than holes is determined as the n-type.
[0395] The binder resin used in the charge generating layer can be selected from a wide range of insulating resins, and the binder resin can be selected from organic photoconductive polymers such as poly-N-vinylcarbazole, polyvinylanthracene, polyvinylpyrene, and polysilane.
[0396] Examples of the binder resin include polyvinyl butyral resin, polyarylate resin (condensation product of bisphenol and aromatic dicarboxylic acid, etc.), polycarbonate resin, polyester resin, phenoxy resin, vinyl chloride-vinyl acetate copolymer, polyamide resin, acrylic resin, polyacrylamide resin, polyvinyl pyridine resin, cellulose resin, urethane resin, epoxy resin, casein, polyvinyl alcohol resin, polyvinyl pyrrolidone resin, etc. Here, "insulation" means that the volume resistivity is 10 13 Ω·cm or more.
[0397] These binder resins may be used alone or in combination of two or more.
[0398] The blending ratio of the charge generating material to the binder resin is preferably, for example, in the range of 10:1 to 1:10 in terms of mass ratio.
[0399] The charge generating layer may contain other well-known additives.
[0400] The formation of the charge generating layer is not particularly limited, and can be performed by a known formation method, for example, by forming a coating film of a charge generating layer-forming coating liquid obtained by adding the above-mentioned components to a solvent, drying the coating film, and heating it as needed. In addition, the formation of the charge generating layer can also be performed by vapor deposition of the charge generating material. The formation of the charge generating layer by vapor deposition is particularly suitable for the case where, for example, a condensed ring aromatic pigment or a perylene pigment is used as the charge generating material.
[0401] Examples of the solvent used for preparing the charge generating layer-forming coating solution include methanol, ethanol, n-propanol, n-butanol, benzyl alcohol, methyl cellosolve, ethyl cellosolve, acetone, methyl ethyl ketone, cyclohexanone, methyl acetate, n-butyl acetate, dioxane, tetrahydrofuran, dichloromethane, chloroform, chlorobenzene, toluene, etc. These solvents may be used alone or in combination of two or more.
[0402] As a method for dispersing particles (e.g., charge generating material) in the coating liquid for forming the charge generating layer, for example, a medium disperser such as a ball mill, a vibrating ball mill, a grinder, a sand mill, a horizontal sand mill, or a stirrer, an ultrasonic disperser, a roll mill, a high-pressure homogenizer, or a medium-free disperser can be used. As a high-pressure homogenizer, for example, a collision method in which the dispersion liquid is subjected to liquid-liquid collision or liquid-wall collision for dispersion under high pressure, a penetration method in which the dispersion liquid is subjected to penetration through a fine flow path for dispersion under high pressure, etc. can be cited.
[0403] In the dispersion, it is effective to set the average particle size of the charge generating material in the charge generating layer forming coating liquid to 0.5 μm or less, for example, preferably 0.3 μm or less, more preferably 0.15 μm or less.
[0404] Examples of a method for applying the charge generating layer forming coating liquid onto the undercoat layer (or the intermediate layer) include common methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, and curtain coating.
[0405] The film thickness of the charge generating layer is preferably set within a range of, for example, 0.1 μm to 5.0 μm, and more preferably within a range of 0.2 μm to 2.0 μm.
[0406] (Charge Transport Layer)
[0407] The charge transport layer is, for example, a layer containing a charge transport material and a binder resin. The charge transport layer may also be a layer containing a polymer charge transport material.
[0408] As charge transport materials, quinone compounds such as p-benzoquinone, chloranil, tetrabromo-p-benzoquinone, anthraquinone, etc.; tetracyano-p-benzoquinone dimethane compounds; fluorene compounds such as 2,4,7-trinitrofluorene; xanthone compounds; benzophenone compounds; cyanoethylene compounds; vinyl compounds and other electron transport compounds. As charge transport materials, hole transport compounds such as triarylamine compounds, benzidine compounds, aryl alkane compounds, aryl substituted vinyl compounds, stilbene compounds, anthracene compounds, hydrazone compounds, etc. can also be mentioned. These charge transport materials are used alone or in combination of two or more, but are not limited to these.
[0409] From the viewpoint of charge mobility, as the charge transport material, for example, a triarylamine derivative represented by the following structural formula (a-1) and a benzidine derivative represented by the following structural formula (a-2) are preferred.
[0410] [Chemical formula 1]
[0411]
[0412] In the structural formula (a-1), Ar T1 ,Ar T2 and Ar T3 Each independently represents a substituted or unsubstituted aryl group, -C6H4-C(R T4 )=C(R T5 )(R T6 ) or -C6H4-CH=CH-CH=C(R T7 )(R T8 ). T4 , R T5 , R T6 , R T7 and R T8 Each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted aryl group.
[0413] Examples of substituents of the above groups include halogen atoms, alkyl groups having 1 to 5 carbon atoms, and alkoxy groups having 1 to 5 carbon atoms. In addition, examples of substituents of the above groups include substituted amino groups substituted with alkyl groups having 1 to 3 carbon atoms.
[0414] [Chemical formula 2]
[0415]
[0416] In the structural formula (a-2), R T91 and R T92 R each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 5 carbon atoms, or an alkoxy group having 1 to 5 carbon atoms.T101 , R T102 , R T111 and R T112 each independently represents a halogen atom, an alkyl group having 1 to 5 carbon atoms, an alkoxy group having 1 to 5 carbon atoms, an amino group substituted by an alkyl group having 1 to 2 carbon atoms, a substituted or unsubstituted aryl group, -C(R T12 )=C(R T13 )(R T14 ) or -CH=CH-CH=C(R T15 )(R T16 ), R T12 , R T13 , R T14 , R T15 and R T16 Each independently represents a hydrogen atom, a substituted or unsubstituted alkyl group, or a substituted or unsubstituted aryl group. Tm1, Tm2, Tn1, and Tn2 each independently represent an integer of 0 or more and 2 or less.
[0417] Examples of substituents of the above groups include halogen atoms, alkyl groups having 1 to 5 carbon atoms, and alkoxy groups having 1 to 5 carbon atoms. In addition, examples of substituents of the above groups include substituted amino groups substituted with alkyl groups having 1 to 3 carbon atoms.
[0418] Here, from the viewpoint of charge mobility, among the triarylamine derivatives represented by the structural formula (a-1) and the benzidine derivatives represented by the structural formula (a-2), for example, those having "-C6H4-CH=CH-CH=C(R T7 )(R T8 )" and triarylamine derivatives having "-CH=CH-CH=C(R T15 )(R T16 )" benzidine derivatives.
[0419] As the polymer charge transport material, known polymer charge transport materials having charge transport properties such as poly-N-vinyl carbazole and polysilane can be cited. In particular, polyester-based polymer charge transport materials are particularly preferred. The polymer charge transport material can be used alone or can be used together with a binder resin.
[0420] The binder resin used for the charge transport layer may include polycarbonate resin, polyester resin, polyarylate resin, methacrylic resin, acrylic resin, polyvinyl chloride resin, polyvinylidene chloride resin, polystyrene resin, polyvinyl acetate resin, styrene-butadiene copolymer, vinylidene chloride-acrylonitrile copolymer, vinyl chloride-vinyl acetate copolymer, vinyl chloride-vinyl acetate-maleic anhydride copolymer, silicone resin, silicone alkyd resin, phenol-formaldehyde resin, styrene-alkyd resin, poly-N-vinyl carbazole, polysilane, etc. Among them, as the binder resin, for example, polycarbonate resin or polyarylate resin is preferred. These binder resins are used alone or in combination of two or more.
[0421] The blending ratio of the charge transport material to the binder resin is preferably, for example, 10:1 to 1:5 in terms of mass ratio.
[0422] The charge transport layer may contain other well-known additives.
[0423] The charge transport layer can be formed without particular limitation and can be formed by a known method, for example, by forming a coating film of a charge transport layer-forming coating liquid obtained by adding the above components to a solvent, drying the coating film, and heating the coating film as necessary.
[0424] As the solvent for preparing the coating solution for forming the charge transport layer, there can be mentioned aromatic hydrocarbons such as benzene, toluene, xylene, and chlorobenzene; ketones such as acetone and 2-butanone; halogenated aliphatic hydrocarbons such as dichloromethane, chloroform, and dichloroethane; cyclic or linear ethers such as tetrahydrofuran and diethyl ether, and other common organic solvents. These solvents can be used alone or in combination of two or more.
[0425] Examples of a coating method for coating the charge transport layer-forming coating liquid on the charge generating layer include common methods such as blade coating, wire bar coating, spray coating, dip coating, bead coating, air knife coating, and curtain coating.
[0426] The film thickness of the charge transport layer is preferably set to, for example, 5 μm or more and 50 μm or less, and more preferably set to be within the range of 10 μm or more and 30 μm or less.
[0427] (Protective layer)
[0428] The protective layer is provided on the photosensitive layer as required. The protective layer is provided, for example, to prevent chemical changes in the photosensitive layer during charging or to further improve the mechanical strength of the photosensitive layer.
[0429] Therefore, for example, a layer composed of a cured film (crosslinked film) is preferably used as the protective layer. Examples of these layers include the layers shown in the following 1) or 2).
[0430] 1) A layer consisting of a cured film of a composition containing a reactive group-containing charge transport material having a reactive group and a charge transport skeleton in the same molecule (i.e., a layer containing a polymer or a crosslinked body of the reactive group-containing charge transport material)
[0431] 2) A layer composed of a cured film of a composition containing a non-reactive charge transport material and a reactive group-containing non-charge transport material having no charge transport skeleton but having a reactive group (i.e., a layer containing a non-reactive charge transport material and a polymer or a crosslinked body of the reactive group-containing non-charge transport material)
[0432] Examples of the reactive group of the reactive group-containing charge transport material include a chain polymerizable group, an epoxy group, -OH, -OR [wherein R represents an alkyl group], -NH2, -SH, -COOH, -SiR Q1 3-Qn (OR Q2 ) Qn [Among them, R Q1 represents a hydrogen atom, an alkyl group, or a substituted or unsubstituted aryl group, R Q2 represents a hydrogen atom, an alkyl group, a trialkylsilyl group, Qn represents an integer of 1 to 3] and the like.
[0433] The chain polymerizable group is not particularly limited as long as it is a functional group capable of free radical polymerization, and is, for example, a functional group having a group containing at least a carbon double bond. Specifically, a group containing at least one selected from a vinyl group, a vinyl ether group, a vinyl sulfide group, a vinyl phenyl group, an acryloyl group, a methacryloyl group, and derivatives thereof may be cited. Among them, since it has excellent reactivity, a group containing at least one selected from a vinyl group, a vinyl phenyl group, an acryloyl group, a methacryloyl group, and derivatives thereof is preferred as the chain polymerizable group.
[0434] The charge transport skeleton of the reactive group-containing charge transport material is not particularly limited as long as it is a known structure in an electrophotographic photoreceptor, and examples thereof include skeletons derived from nitrogen-containing hole transport compounds such as triarylamine compounds, benzidine compounds, and hydrazone compounds, which are conjugated structures with nitrogen atoms. Among them, for example, a triarylamine skeleton is preferred.
[0435] The reactive group-containing charge transport material, the non-reactive charge transport material, and the reactive group-containing non-charge transport material having a reactive group and a charge transport skeleton may be selected from known materials.
[0436] The protective layer may contain other well-known additives.
[0437] The protective layer can be formed without particular limitation and can be formed by a known method, for example, by forming a coating film of a protective layer-forming coating liquid obtained by adding the above components to a solvent, drying the coating film, and curing it by heating or the like as needed.
[0438] Examples of the solvent used to prepare the protective layer-forming coating solution include aromatic solvents such as toluene and xylene; ketone solvents such as methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester solvents such as ethyl acetate and butyl acetate; ether solvents such as tetrahydrofuran and dioxane; cellolytic solvents such as ethylene glycol monomethyl ether; alcohol solvents such as isopropyl alcohol and butanol, etc. These solvents may be used alone or in combination of two or more.
[0439] Furthermore, the protective layer-forming coating liquid may be a solvent-free coating liquid.
[0440] Examples of a method for applying the protective layer-forming coating liquid onto a photosensitive layer (eg, charge transport layer) include common methods such as dip coating, push coating, wire bar coating, spray coating, blade coating, air knife coating, and curtain coating.
[0441] The film thickness of the protective layer is preferably set to, for example, 1 μm or more and 20 μm or less, and more preferably set to be within the range of 2 μm or more and 10 μm or less.
[0442] (Single-layer photosensitive layer)
[0443] The single-layer photosensitive layer (charge generation / charge transport layer) is a layer containing, for example, a charge generation material and a charge transport material and, if necessary, a binder resin and other known additives. These materials are the same as those described for the charge generation layer and the charge transport layer.
[0444] Furthermore, the content of the charge generating material in the single-layer photosensitive layer is preferably, for example, 0.1% by mass or more and 10% by mass or less, and preferably 0.8% by mass or more and 5% by mass or less, relative to the total solid content. Furthermore, the content of the charge transporting material in the single-layer photosensitive layer is preferably, for example, 5% by mass or more and 50% by mass or less, relative to the total solid content.
[0445] The method for forming the single-layer type photosensitive layer is the same as the method for forming the charge generating layer and the charge transporting layer.
[0446] The film thickness of the single-layer photosensitive layer is, for example, preferably 5 μm to 50 μm, and preferably 10 μm to 40 μm.
[0447] [Structure of Image Forming Apparatus (and Processing Cartridge)]
[0448] The image forming device involved in this embodiment comprises: an image holder; a charging component for charging the surface of the image holder; an electrostatic latent image forming component for forming an electrostatic latent image on the surface of the charged image holder; a developing component for containing an electrostatic latent image developer containing a colorant having colorant particles, and developing the electrostatic latent image formed on the surface of the image holder into a colorant image by the electrostatic latent image developer; a transfer component for transferring the colorant image formed on the surface of the image holder to the surface of a recording medium; and a cleaning device having a cleaning scraper, which contacts and cleans the outer peripheral surface of the cleaning image holder.
[0449] Well-known image forming devices such as a device having a transfer member for transferring a colorant image on an image holder to a recording medium via a secondary transfer member (for example, a secondary transfer belt); a device having a fixing member for fixing the colorant image transferred to the surface of the recording medium; a device having a cleaning device for cleaning the surface of the image holder after transferring the colorant image but before charging; a device having a static elimination device for eliminating static electricity by irradiating the surface of the image holder with static elimination light after transferring the colorant image and before charging; a device having an image holder heating member for increasing the temperature of the image holder to lower the relative temperature, etc. are applicable to the image forming device involved in this embodiment.
[0450] The image forming apparatus according to the present embodiment may be any of a dry developing system image forming apparatus and a wet developing system (development system using a liquid developer) image forming apparatus.
[0451] In the image forming apparatus according to the present embodiment, for example, the portion including the image holder may be a cartridge structure (process cartridge) that is detachable from the image forming apparatus. As the process cartridge, for example, a process cartridge including a toner image forming device and a transfer device is preferably used.
[0452] (Image Forming Method)
[0453] The image forming method involved in this embodiment includes: a charging process, which charges the surface of the image retaining body; an electrostatic latent image forming process, which forms an electrostatic latent image on the surface of the charged image retaining body; a developing process, which develops the electrostatic latent image formed on the surface of the image retaining body into a colorant image by using an electrostatic latent image developer containing a colorant having colorant particles; a transfer process, which transfers the colorant image formed on the surface of the image retaining body to the surface of a recording medium; and a cleaning process, which brings a cleaning scraper into contact with the outer peripheral surface of the image retaining body and cleans it.
[0454] In the toner particles, the releasing agent present in a region within 800 nm from the surface accounts for 70% or more of the releasing agent in the entire toner particles, and the melting temperature of the releasing agent is 65° C. or more and 80° C. or less.
[0455] The cleaning blade is made of polyurethane resin, and the total amount of F and Si present within 200 nm from the surface of the cleaning blade in contact with the image holding member accounts for 75% or more of the total amount of F and Si present within 5 μm from the surface.
[0456] Hereinafter, an example of the image forming apparatus and the image forming method according to the present embodiment will be described with reference to the accompanying drawings. However, the image forming apparatus and the image forming method according to the present embodiment are not limited thereto. In addition, the main parts shown in the drawings will be described, and the description of other parts will be omitted.
[0457] Figure 2 It is a schematic configuration diagram showing an example of the image forming apparatus according to the present embodiment.
[0458] like Figure 2 As shown, the image forming apparatus 100 according to the present embodiment includes a process cartridge 300 having an electrophotographic photoreceptor 7 (an example of an image holding member), an exposure device 9 (an example of an electrostatic latent image forming member), a transfer device 40 (a primary transfer device), and an intermediate transfer member 50. In addition, in the image forming apparatus 100, the exposure device 9 is arranged at a position capable of exposing the electrophotographic photoreceptor 7 from the opening of the process cartridge 300, and the transfer device 40 is arranged at a position opposed to the electrophotographic photoreceptor 7 with the intermediate transfer member 50 interposed therebetween, and the intermediate transfer member 50 is arranged such that a part thereof contacts the electrophotographic photoreceptor 7. Although not shown in the figure, a secondary transfer device is further provided for transferring the toner image transferred to the intermediate transfer member 50 to a recording medium (e.g., paper). In addition, the intermediate transfer member 50, the transfer device 40 (a primary transfer device), and the secondary transfer device (not shown in the figure) correspond to an example of a transfer member.
[0459] Figure 2 The process box 300 in the embodiment integrally supports the electrophotographic photoreceptor 7, the charging device 8 (an example of a charging member), the developing device 11 (an example of a developing member), and the cleaning device 13 in the housing. The cleaning device 13 has a cleaning blade 131, and the cleaning blade 131 is configured to contact the surface of the electrophotographic photoreceptor 7. In addition, the cleaning member may be a conductive or insulating fibrous member instead of the cleaning blade 131, and it may be used alone or simultaneously with the cleaning blade 131.
[0460] In addition, Figure 2In the example shown, as the image forming apparatus, a fibrous member 132 (roller-shaped) for supplying lubricant 14 to the surface of electrophotographic photoreceptor 7 and a fibrous member 133 (flat brush-shaped) for assisting cleaning are provided, but these may be arranged as necessary.
[0461] Hereinafter, each structure of the image forming apparatus according to the present embodiment will be described.
[0462] -Charging device-
[0463] As the charging device 8, for example, a contact charger using a conductive or semi-conductive charging roller, a charging brush, a charging film, a charging rubber blade, a charging hose, etc. can be used. In addition, a non-contact roller charger, a scorotron charger using corona discharge, a corotron charger, or a corotron charger, which are known in themselves, can also be used.
[0464] -Exposure device-
[0465] As the exposure device 9, for example, there can be cited an optical system device that exposes semiconductor laser, LED light, liquid crystal shutter light, etc. on the surface of the electrophotographic photoreceptor 7 to a predetermined pattern. The wavelength of the light source is set within the spectral sensitivity range of the electrophotographic photoreceptor. As the wavelength of the semiconductor laser, near-infrared light with an oscillation wavelength near 780nm is the mainstream. However, it is not limited to this wavelength. As an oscillation wavelength laser or a blue laser in the 600nm band, a laser with an oscillation wavelength in the range of more than 400nm and less than 450nm can be used. In addition, a surface-emitting laser light source that can output multiple light beams to form a color image is also effective.
[0466] -Developing device-
[0467] As the developing device 11, for example, a general developing device that performs development by contacting or non-contacting the developer can be cited. As the developing device 11, there is no particular limitation as long as it has the above-mentioned function, and it can be selected according to the purpose. For example, a known developer having a function of attaching a single-component developer or a two-component developer to the electrophotographic photoreceptor 7 using a brush, a roller, etc. can be cited. Among them, for example, a developer using a developing roller that holds the developer on the surface is preferably used.
[0468] The developer used in the developing device 11 may be a single-component developer containing a single toner or a two-component developer containing a toner and a carrier. Furthermore, the developer may be magnetic or non-magnetic. These developers are suitable for use with known developers.
[0469] -Cleaning device-
[0470] The cleaning device 13 is a cleaning blade type device including a cleaning blade 131 .
[0471] -Transfer device-
[0472] Examples of the transfer device 40 include a transfer charger known per se, such as a contact transfer charger using a belt, a roller, a film, a rubber blade, or the like, a scorotron transfer charger using corona discharge, or a corotron transfer charger.
[0473] -Intermediate transfer body-
[0474] A belt-shaped transfer body (intermediate transfer belt) containing polyimide, polyamideimide, polycarbonate, polyarylate, polyester, rubber, etc. imparted with semiconductivity is used as the intermediate transfer body 50. In addition, a roller-shaped transfer body can be used as the intermediate transfer body.
[0475] Figure 3 It is a schematic configuration diagram showing another example of the image forming apparatus according to the present embodiment.
[0476] Figure 3 The image forming apparatus 120 shown is a multi-color image forming apparatus of a tandem type equipped with four process cartridges 300. In the image forming apparatus 120, four process cartridges 300 are arranged side by side on the intermediate transfer body 50, and one electrophotographic photoreceptor is used for each color. The image forming apparatus 120 is a tandem type, and has the same structure as the image forming apparatus 100 except that it is a tandem type.
[0477] As mentioned above, although this embodiment was demonstrated, it is not interpreted as being limited to the said embodiment, Various deformation|transformation, change, and improvement are possible.
[0478] Example
[0479] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the following examples. In the following description, "parts" and "%" are based on mass unless otherwise specified.
[0480] [Example 1]
[0481] <Preparation of electrostatic latent image developer>
[0482] -Preparation of amorphous polyester resin dispersion-
[0483] (Preparation of polyester resin dispersion (APE1))
[0484] Terephthalic acid: 30 mol parts
[0485] Fumaric acid: 70 mol parts
[0486] Bisphenol A ethylene oxide adduct: 5 mol parts
[0487] Bisphenol A propylene oxide adduct: 95 mol parts
[0488] The above materials were placed in a 5-liter flask equipped with a stirring device, a nitrogen inlet pipe, a temperature sensor, and a distillation tower, and the temperature was raised to 210°C over 1 hour. 1 part of tetraethoxytitanium was added to 100 parts of the above materials. While distilling off the generated water, the temperature was raised to 230°C over 0.5 hours, and the dehydration condensation reaction was continued at this temperature for 1 hour, and then the reactant was cooled. In this way, a polyester resin with a weight average molecular weight of 18,500, an acid value of 14 mgKOH / g, and a glass transition temperature of 59°C was synthesized.
[0489] After adding 40 parts of ethyl acetate and 25 parts of 2-butanol to a container equipped with a temperature regulating member and a nitrogen replacement member to prepare a mixed solvent, 100 parts of a polyester resin was gradually added to dissolve it, and a 10% by mass ammonia aqueous solution (equivalent to 3 times the acid value of the resin in terms of molar ratio) was added and stirred for 30 minutes.
[0490] Next, the interior of the container was replaced with dry nitrogen, and the temperature was maintained at 40°C. While stirring the mixed solution, 400 parts of deionized water was added dropwise at a rate of 2 parts / min to emulsify the mixture. After the addition was completed, the emulsion was returned to room temperature (20°C to 25°C), and while stirring, dry nitrogen was bubbled for 48 hours to reduce ethyl acetate and 2-butanol to less than 1,000 ppm, thereby obtaining a resin particle dispersion in which resin particles with a volume average particle size of 200 nm were dispersed. Deionized water was added to the resin particle dispersion to adjust the solid content to 20% by mass, which was used as a polyester resin particle dispersion (APE1).
[0491] -Preparation of Colorant Particle Dispersion-
[0492] (Preparation of Colorant Particle Dispersion Liquid (Black Pigment Dispersion Liquid))
[0493] Carbon black (Regal 330 manufactured by Cabot Corporation): 250 parts
[0494] Anionic surfactant (NEOGEN SC manufactured by DKS Co. Ltd.): 33 parts (active ingredient: 60%).
[0495] 8% relative to colorant)
[0496] Deionized water: 750 parts
[0497] 280 parts of deionized water and 33 parts of anionic surfactants were put into a stainless steel container whose height of the liquid level became about 1 / 3 of the height of the container when all the above components were put into the container. After the surfactant was fully dissolved, all the solid solution pigments were put into the container, and a stirrer was used to stir until there was no pigment that was not wetted, and defoaming was fully carried out. After defoaming, the remaining deionized water was added, and after a homogenizer (IKA company system, ULTRA TURRAX T50) was used to disperse for 10 minutes at 5000 revolutions, a stirrer was used to stir for 1 day and night, and defoaming was carried out. After defoaming, a homogenizer was used again to disperse for 10 minutes at 6000 revolutions, and a stirrer was used to stir for 1 day and night, and defoaming was carried out. Then, a high-pressure impact dispersion machine ULTIMAIZER (SUGINOMACHINE LIMITED system, HJP30006) was used to disperse the dispersion liquid with a pressure of 240MPa. According to the total loading amount and the processing capacity of the device, about 25 dispersions were carried out. The obtained dispersion was left for 72 hours, the precipitate was removed, and deionized water was added to adjust the solid content concentration to 15% to obtain a colorant particle dispersion. The volume average particle size D50 of the particles in the colorant particle dispersion was 135 nm.
[0498] (Preparation of Release Agent Dispersion)
[0499] (Preparation of Release Agent Dispersion (WAX1))
[0500] Paraffin wax (HNP9 manufactured by NIPPON SEIRO CO., LTD., melting temperature 75°C): 270 parts
[0501] Anionic surfactant (NEOGEN RK manufactured by DKS Co. Ltd., active ingredient amount: 60%): 13.5 parts (3.0% based on the release agent in terms of active ingredient)
[0502] Deionized water: 21.6 parts
[0503] The above components were mixed, and the release agent was dissolved in a pressure-dispensing homogenizer (manufactured by Gaulin Co., Ltd., Gaulin Homogenizer) at an internal liquid temperature of 120°C, and then dispersed at a dispersion pressure of 5 MPa for 120 minutes, and then dispersed at 40 MPa for 360 minutes, and cooled to obtain a release agent dispersion (WAX1). The volume average particle size D50 of the particles in the release agent dispersion (WAX1) was 225 nm. Then, deionized water was added to adjust the solid content concentration to 20.0%.
[0504] -Preparation of mixed particle dispersion-
[0505] (Preparation of mixed particle dispersion (RW1))
[0506] After mixing 150 parts of a polyester resin particle dispersion (APE1), 20 parts of a release agent particle dispersion (WAX1) and 2.9 parts of an anionic surfactant (Dowfax2A1 manufactured by The Dow Chemical Company), 1.0% nitric acid was added at 25°C to adjust the pH to 3.0, thereby obtaining a mixed particle dispersion (RW1).
[0507] -Preparation of toner-
[0508] Polyester resin particle dispersion (APE1): 700 parts
[0509] Colorant particle dispersion: 133 parts
[0510] Deionized water: 400 parts
[0511] Anionic surfactant (manufactured by The Dow Chemical Company, Dowfax 2A1): 2.9 parts
[0512] The above components were placed in a 3-liter reaction container equipped with a thermometer, a pH meter, and a stirrer, and 1.0% nitric acid was added at a temperature of 25°C to adjust the pH to 3.0. Then, 130 parts of the prepared aluminum sulfate aqueous solution were added while dispersing at 5,000 rpm using a homogenizer (IKA Japan: ULTRA TUR RAX T50) and dispersion was carried out for 6 minutes.
[0513] Then, a stirrer and a hood heater were set in the reaction vessel, and the rotation speed of the stirrer was adjusted so that the slurry was fully stirred, while the temperature was raised to 40°C at a heating rate of 0.2°C / min, and the temperature was raised at a heating rate of 0.05°C / min from above 40°C. Every 10 minutes, the particle size was measured using Multisizer II (aperture: 50μm, manufactured by Beckman Coulter, Inc.). When the volume average particle size reached 5.0μm, the temperature was maintained, and 450 parts of the mixed particle dispersion (RW1) were added for 5 minutes. After keeping it for 30 minutes, the pH was adjusted to 9.0 using a 1% sodium hydroxide aqueous solution. Then, every 5°C, the pH was adjusted to 9.0 in the same manner, while the temperature was raised to 90°C at a heating rate of 1°C / min, and maintained at 98°C. The particle shape and surface properties were observed using an optical microscope and a scanning electron microscope (FE-SEM). As a result, aggregation of particles was confirmed at 10.0 hours, so the container was cooled to 30° C. using cooling water over 5 minutes.
[0514] The cooled slurry was passed through a nylon mesh with a pore size of 15 μm to remove coarse powder, and the toner slurry after passing through the mesh was filtered under reduced pressure using an aspirator. The toner remaining on the filter paper was crushed into fine particles by hand, and deionized water 10 times the amount of the toner was added at a temperature of 30°C, and stirred and mixed for 30 minutes. Next, the toner was filtered under reduced pressure using an aspirator, and the toner remaining on the filter paper was crushed into fine particles by hand, and deionized water 10 times the amount of the toner was added at a temperature of 30°C. After stirring and mixing for 30 minutes, the toner was filtered under reduced pressure again using an aspirator, and the conductivity of the filtrate was measured. This operation was repeated until the conductivity of the filtrate became less than 10 μS / cm, and the toner was washed. After the washed toner was crushed into fine particles using a wet dry granulator (COMIL), it was vacuum dried in an oven at 35°C for 36 hours to obtain toner particles.
[0515] Then, 3.3 parts of silica particles were added as an external additive to 100 parts of the toner particles, and then mixed for 3 minutes at a peripheral speed of 30 m / s using a Henschel mixer. Then, the mixture was sieved using a vibration sieve with an aperture of 45 μm to obtain a toner.
[0516] -Carrier production-
[0517] 500 parts of spherical magnetite particle powder with a volume average particle size of 0.18 μm were added to a Henschel mixer and stirred thoroughly. Then, 5 parts of a titanate coupling agent were added, the temperature was raised to 95° C., and the mixture was stirred for 30 minutes to obtain spherical magnetite particles coated with a titanate coupling agent.
[0518] Next, 6 parts of phenol, 10 parts of 30% formalin, 500 parts of magnetite particles, 7 parts of 25% ammonia water and 400 parts of water were placed in a 1L four-necked flask and mixed and stirred. Then, while stirring, the temperature was raised to 90°C within 60 minutes, and the reaction was carried out at the same temperature for 180 minutes, then cooled to 30°C, 500 ml of water was added, the supernatant was removed, and the precipitate was washed with water. It was dried at 180°C under reduced pressure, and the coarse powder was removed using a sieve with a mesh of 106 μm to obtain core particles with an average particle size of 38 μm.
[0519] Next, 200 parts of toluene and 35 parts of a styrene-methyl methacrylate copolymer (component molar ratio of 10:90, weight average molecular weight of 160,000) were stirred in a stirrer for 90 minutes to obtain a coating resin solution.
[0520] 1000 parts of the core particles and 70 parts of the coating resin solution were placed in a vacuum degassing type kneading coater (the gap between the rotor and the wall surface was 35 mm), maintained at 65°C, stirred at 30 rpm for 30 minutes, and then the temperature was brought to 88°C, the pressure was reduced, toluene was distilled off, degassed and dried. Then, it was passed through a sieve with a mesh size of 75 μm. The shape factor SF2 of the carrier was 104.
[0521] -Production of developer-
[0522] 8 parts of toner and 100 parts of carrier were mixed with a V mixer to prepare a developer.
[0523] -Toner Properties-
[0524] The ratio of the releasing agent present in the region within 800 nm from the surface of the toner particles to the releasing agent in the entire toner particles (surface ratio of the releasing agent) was measured by the above method. The melting temperature of the releasing agent was also measured by the above method.
[0525] <Cleaning Blade Production>
[0526] At 115°C, 100 parts by mass of polycaprolactone polyol (molecular weight 2000) as a high molecular weight polyol component and 58 parts by mass of 4,4'-diphenylmethane diisocyanate (MDI: manufactured by DIC Corporation) as a polyisocyanate component were reacted for 20 minutes. Then, 6.1 parts by mass of 1,4-butanediol and 2.6 parts by mass of trimethylolpropane as low molecular weight polyol components were mixed and heated and cured for 40 minutes in a mold maintained at 140°C. After molding, a rubber elastic body cut into a width of 14 mm, a thickness of 1.9 mm, and a length of 330 mm was prepared, and the rubber elastic body was bonded to a support plate to prepare a blade substrate.
[0527] 80 parts by mass of ethyl acetate as an organic solvent, 25 parts by mass of 4,4′-diphenylmethane diisocyanate (MDI: “Millionate MT” manufactured by TOSOH CORPORATION, melting point: 38° C.) as an isocyanate compound, and 5 parts by mass of a silicone-modified acrylic polymer (8BS-9000; manufactured by Taisei Fine Chemical Co., Ltd.) as an acrylic polymer having a siloxane bond (specific polymer) were dispersed and mixed in a ball mill for 5 hours to obtain a surface treatment liquid.
[0528] The scraper substrate was immersed in the surface treatment liquid for 60 seconds while the surface treatment liquid was kept at 23°C, and then dried for 1 minute at room temperature (25°C). Then, the surface of the dried scraper substrate was wiped clean with a sponge containing a small amount of toluene, and then dried for 1 minute at 25°C, and heated in an oven kept at 25°C for 50 minutes to obtain a cleaning scraper.
[0529] -Physical properties of cleaning blade-
[0530] The above method was used to measure the ratio of the total amount of F and Si present within 200 nm from the surface in contact with the image holder to the total amount of F and Si present within 5 μm from the surface (surface ratio of F and Si), the total amount of F and Si present on the surface in contact with the image holder (surface F and Si amount (atm%)), the total amount of F and Si present at a position 50 nm from the surface in contact with the image holder (50 nm position F and Si amount (atm%)) and the 100% modulus (MPa) of the cleaning scraper.
[0531] <Production of photoreceptor>
[0532] As the polyester resin (1), a polyester resin (PE1) composed of 50 mol% of the dicarboxylic acid units (A2-3) and 50 mol% of the diol units (B1-4) and having a weight average molecular weight of 50,000 was prepared.
[0533] -Formation of lower coating layer-
[0534] As the conductive substrate, an aluminum cylindrical tube having an outer diameter of 30 mm, a length of 250 mm, and a wall thickness of 1 mm was prepared.
[0535] Zinc oxide (average particle size 70 nm, specific surface area 15 m 2 / g, TAYCA CORPORATION) 100 parts and 500 parts of toluene were stirred and mixed, and 1.3 parts of a silane coupling agent (trade name: KBM603, Shin-Etsu Chemical Co., Ltd., N-2-(aminoethyl)-3-aminopropyltrimethoxysilane) were added and stirred for 2 hours. Then, toluene was distilled off under reduced pressure, and calcination was performed at 120° C. for 3 hours to obtain zinc oxide surface-treated with a silane coupling agent.
[0536] 110 parts of surface-treated zinc oxide and 500 parts of tetrahydrofuran were stirred and mixed, and a solution of 0.6 parts of alizarin dissolved in 50 parts of tetrahydrofuran was added, followed by stirring at 50° C. for 5 hours. Then, the solid content was filtered out by reduced pressure filtration and dried at 60° C. to obtain zinc oxide to which alizarin was imparted.
[0537] Mix 60 parts of zinc oxide imparting alizarin, 13.5 parts of curing agent (blocked isocyanate, trade name: SUMIDUR3175, manufactured by Sumitomo Bayer Urethane Co., Ltd.) and 15 parts of butyral resin (trade name: S-LEC BM-1, manufactured by SEKISUI CHEMICAL CO., LTD.) dissolved in 68 parts of methyl ethyl ketone to obtain 100 parts of the solution and 5 parts of methyl ethyl ketone, and disperse them in a sand mill for 2 hours using 1 mmφ glass beads to obtain a dispersion. 0.005 parts of dioctyltin dilaurate and 4 parts of silicone resin particles (trade name: Tospea rl145, manufactured by Momentiveperformance Materials Inc.) were added to the dispersion as catalysts to obtain a coating solution for forming an undercoat layer. The coating solution for forming an undercoat layer was applied to the outer peripheral surface of the conductive substrate by dip coating, and dried and cured at 170°C for 40 minutes to form an undercoat layer. The average thickness of the undercoat layer was set to 25 μm.
[0538] -Formation of Charge Generation Layer-
[0539] A mixture consisting of 15 parts of hydroxygallium phthalocyanine (having diffraction peaks at positions of at least 7.5°, 9.9°, 12.5°, 16.3°, 18.6°, 25.1° and 28.3° in the Bragg angle (2θ±0.2°) of the X-ray diffraction spectrum using Cukα characteristic X-rays) as a charge generating material, 10 parts of a vinyl chloride-vinyl acetate copolymer resin (trade name: VMCH, manufactured by Nippon Unicar Company Limited) as a binder resin, and 200 parts of n-butyl acetate was dispersed in a sand mill for 4 hours using glass beads having a diameter of 1 mm. 175 parts of n-butyl acetate and 180 parts of methyl ethyl ketone were added to the dispersion, and stirred to obtain a coating liquid for forming a charge generating layer. The coating liquid for forming a charge generating layer was dip-coated on the undercoat layer and dried at room temperature (25°C±3°C) to form a charge generating layer having an average thickness of 0.18 μm.
[0540] -Formation of Charge Transport Layer-
[0541] 60 parts of polyester resin (PE1) as a binder resin and 40 parts of (CTM-1) as a charge transport material were dissolved in 270 parts of tetrahydrofuran and 30 parts of toluene to obtain a coating solution for forming a charge transport layer. The coating solution for forming a charge transport layer was dip-coated on the charge generating layer and dried at 145°C for 30 minutes to form a charge transport layer with an average thickness of 40 μm.
[0542] [Chemical formula 3]
[0543]
[0544] <Image forming device>
[0545] The obtained products were installed in an image forming apparatus "Apeos C-8180 manufactured by FUJIFILM Business Innovation Corp." as an electrostatic latent image developer, a photoreceptor, and a cleaning blade for the photoreceptor.
[0546] [Examples 2 to 19, Comparative Examples 1 to 2]
[0547] <Preparation of electrostatic latent image developer>
[0548] In Example 1, a release agent is selected for the preparation of a release agent dispersion, and the amount of a mixed particle dispersion (RW1) is adjusted when preparing a colorant, thereby preparing colorant particles that satisfy the "surface ratio of the release agent (%)" and "melting temperature of the release agent (°C)" recorded in Tables 1 and 2 to obtain an electrostatic latent image developer.
[0549] In addition, as the release agent having the melting temperature shown in Table 1, the following compounds were used alone or in combination.
[0550] · Paraffin wax (manufactured by NIPPON SEIRO CO., LTD., melting temperature 64°C)
[0551] ·Ester wax (manufactured by NOF CORPORATION, melting temperature 82°C)
[0552] <Cleaning Blade Production>
[0553] In Example 1, the amount of 4,4'-diphenylmethane diisocyanate (MDI: "Millionate MT" manufactured by TOSO H CORPORATION, melting point: 38°C) when forming the cleaning blade was changed to the amount described in Table 1. In addition, regarding the obtained blade substrate, the composition of the surface treatment liquid used in the surface modification treatment of the contact portion and the conditions of the surface heat treatment were changed to the composition and conditions described in Table 1, and a cleaning blade satisfying the "surface ratio of F and Si (%)", "surface F and Si amount (atm%)", "50nm position F and Si amount (atm%)", and "100% modulus (MPa)" described in Table 2 was produced. In addition, the pressing force NF (gf / mm), the pressing angle WA (°), and NF×WA when the obtained cleaning blade was attached to the image forming apparatus were set to the conditions described in Table 2.
[0554] In addition, as components of the surface treatment liquid shown in Table 1, the following compounds were used.
[0555] Silicon-modified acrylic polymer (8BS-9000; manufactured by Taisei Fine Chemical Co., Ltd.)
[0556] Fluorosilicone-modified acrylic polymer (8FS-009; manufactured by Taisei Fine Chemical Co., Ltd.)
[0557] ・Isocyanate compound (MDI: "Millionate MT" manufactured by TOSOH CORPORATION, melting point: 38°C)
[0558] <Evaluation test>
[0559] Using the image forming apparatus prepared in each example and comparative example, 50,000 images with an image density of 0.5% were printed on A4 paper in a normal temperature and low humidity environment (21° C. 10%). The image quality and cleaning blade after printing were evaluated according to the following criteria.
[0560] Film forming
[0561] The observed image of 100 μm square on the surface of the photoreceptor was binarized, and the area ratio occupied by the attached matter was obtained and evaluated according to the following criteria.
[0562] - Benchmarks -
[0563] A: Not happening.
[0564] B: Some film formation of external additives occurs. This level is sufficiently acceptable for practical use.
[0565] C: Filming occurs. This is a level that is acceptable in practical use.
[0566] D: Filming occurs. This level is not acceptable for practical use.
[0567] E: Filming occurs frequently. This level is not acceptable in actual use.
[0568] Scraper wear
[0569] The wear depth of the contact portion of the cleaning blade was measured by observing the cross-sectional profile using a laser microscope VK-9500 manufactured by KEYENCE CORPORATION.
[0570] - Benchmarks -
[0571] The wear depth of the cleaning blade was measured and evaluated according to the following criteria.
[0572] A: Wear depth <0.5μm
[0573] B: 0.5μm≤wear depth<1.0μm
[0574] C: 1.0μm≤wear depth<1.5μm
[0575] D: 1.5μm≤wear depth<2.0μm
[0576] E: 2.0μm≤wear depth<2.5μm[Table 1]
[0577]
[0578] [Table 2]
[0579]
[0580] As shown in Table 1 and Table 2, it can be seen that the image forming apparatus of this embodiment can suppress toner filming on the photoreceptor surface and suppress abrasion of the cleaning blade compared to the comparative example.
[0581] This embodiment includes the following aspects.
[0582] (((1)))An image forming apparatus comprising:
[0583] Image holding body;
[0584] a charging member for charging the surface of the image holding member;
[0585] an electrostatic latent image forming member for forming an electrostatic latent image on the charged surface of the image holding member;
[0586] A developing member containing an electrostatic latent image developer containing a toner having toner particles, wherein a release agent existing in a region within 800 nm from the surface of the toner particles accounts for 70% or more of the entire release agent of the toner particles, and a melting temperature of the release agent is 65° C. or more and 80° C. or less, and an electrostatic latent image formed on the surface of the image holding member is developed into a toner image by the electrostatic latent image developer;
[0587] a transfer member that transfers the toner image formed on the surface of the image holding body to a surface of a recording medium; and
[0588] A cleaning device having a cleaning scraper which contacts and cleans the outer peripheral surface of the image holder and is made of a polyurethane resin, wherein the total amount of F and Si present within 200 nm from the surface in contact with the image holder accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface.
[0589] (((2)))The image forming apparatus according to (((1))), wherein:
[0590] The releasing agent existing in a region within 800 nm from the surface of the toner particle accounts for 75% or more of the releasing agent in the entire toner particle.
[0591] (((3)))The image forming apparatus according to (((1))) or (((2))), wherein:
[0592] The melting temperature of the release agent is 70° C. or higher and 75° C. or lower.
[0593] (((4)))The image forming apparatus according to any one of (((1))) to (((3))), wherein:
[0594] The 100% modulus at 23° C. of the surface of the cleaning blade in contact with the image holding body is 11 MPa or more and 22 MPa or less.
[0595] (((5)))The image forming apparatus according to (((4))), wherein:
[0596] The 100% modulus at 23° C. of the surface of the cleaning blade in contact with the image holding body is 15 MPa or more and 18 MPa or less.
[0597] (((6)))The image forming apparatus according to any one of (((1))) to (((5))), wherein:
[0598] In the cleaning blade, the total amount of F and Si present within 200 nm from the surface in contact with the image holding member accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface.
[0599] (((7)))The image forming apparatus according to any one of (((1))) to (((6))), wherein:
[0600] In the cleaning blade, a total amount of F and Si present on a surface in contact with the image holding member is 15 atm % or more.
[0601] (((8)))An image forming apparatus according to (((7))), wherein:
[0602] In the cleaning blade, a total amount of F and Si present on a surface in contact with the image holding member is 18 atm % or more and 25 atm % or less.
[0603] (((9)))The image forming apparatus according to any one of (((1))) to (((8))), wherein:
[0604] In the cleaning blade, the total amount of F and Si present at a position 50 nm from the surface in contact with the image holding member is 0.3 atm % or more.
[0605] (((10)))An image forming device according to (((9))), wherein:
[0606] In the cleaning blade, a total amount of F and Si present at a position 50 nm from a surface in contact with the image holding member is 1.0 atm % or more and 2.0 atm % or less.
[0607] (((11)))The image forming apparatus according to any one of (((1))) to (((10))), wherein:
[0608] The cleaning blade contains a silicone-based polymer in a surface layer that contacts the image holding member.
[0609] (((12)))The image forming apparatus according to any one of (((1))) to (((11))), wherein:
[0610] A product of a static pressing force NF and a pressing angle WA between the cleaning blade and the image holding member is 40° or more and 60° or less.
[0611] (((13)))An image forming method comprising:
[0612] A charging process to charge the surface of the image holding body;
[0613] An electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the image holding member;
[0614] A developing step of developing the electrostatic latent image formed on the surface of the image holding member into a toner image by an electrostatic latent image developer, wherein the electrostatic latent image developer contains a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less;
[0615] a transfer step of transferring the toner image formed on the surface of the image holding body to the surface of a recording medium; and
[0616] The cleaning process involves contacting a cleaning blade with the peripheral surface of the image holder and cleaning it, wherein the cleaning blade is made of a polyurethane resin, and the total amount of F and Si within 200 nm of the surface in contact with the image holder accounts for more than 75% of the total amount of F and Si within 5 μm of the surface.
[0617] According to the invention involved in (((1))), there is provided an image forming device in which colorant filming on the surface of the image holder is suppressed and wear of the cleaning scraper is suppressed, compared to an image forming device having a cleaning scraper in which the total amount of F and Si present within 200nm from the surface in contact with the image holder is less than 75% of the total amount of F and Si present within 5μm from the surface.
[0618] According to the invention of (((2))), an image forming apparatus having excellent low-temperature fixing property of an image is provided, compared with an image forming apparatus in which the amount of release agent present in a region within 800 nm from the surface of the toner particle is less than 75% of the release agent in the entire toner particle.
[0619] According to the invention involved in (((3))), an image forming device is provided that has excellent low-temperature fixing properties of an image compared to an image forming device in which the melting temperature of a release agent exceeds 75°C, and an image forming device is provided that suppresses colorant filming on the surface of an image retaining body compared to an image forming device in which the melting temperature of a release agent is lower than 70°C.
[0620] According to the invention involved in (((4))) or (((5))), there is provided an image forming device in which the 100% modulus at 23°C of the surface of the cleaning scraper in contact with the image retainer is less than 11 MPa, and the streaky image defects caused by partial lifting of the scraper are suppressed; and there is provided an image forming device in which the 100% modulus at 23°C of the surface of the cleaning scraper in contact with the image retainer exceeds 22 MPa, and the colorant filming on the surface of the image retainer is suppressed.
[0621] According to the invention involved in (((6))), there is provided an image forming device in which colorant filming on the surface of the image holder is suppressed and wear of the cleaning scraper is suppressed, compared to an image forming device having a cleaning scraper in which the total amount of F and Si present within 200nm from the surface in contact with the image holder is less than 85% of the total amount of F and Si present within 5μm from the surface.
[0622] According to the invention involved in (((7))) or (((8))), there is provided an image forming device in which colorant filming on the surface of the image retaining body is suppressed and wear of the cleaning scraper is suppressed, compared to an image forming device having a cleaning scraper in which the total amount of F and Si present on the surface in contact with the image retaining body is less than 15 atm%.
[0623] According to the invention involved in (((9))) or (((10))), there is provided an image forming device in which, compared with an image forming device having a cleaning scraper in which the total amount of F and Si present at a position 50nm away from the surface in contact with the image retainer is less than 0.3atm%, the occurrence of colorant filming on the surface of the image retainer is suppressed and the wear of the cleaning scraper over time is also suppressed.
[0624] According to the invention of (((11))), there is provided an image forming device in which the formation of colorant film on the surface of the image holder is suppressed and the wear of the cleaning blade is suppressed, compared to an image forming device having a cleaning blade whose surface layer in contact with the image holder contains a fluorine-based compound but does not contain a silicone-based polymer.
[0625] According to the invention involved in (((12))), there is provided an image forming device which suppresses the occurrence of colorant leakage at the contact position between the image retaining body and the cleaning scraper when the product of the static pressing force NF and the pressing angle WA between the cleaning scraper and the image retaining body is less than 40, and there is provided an image forming device which further suppresses the occurrence of colorant filming on the surface of the image retaining body when the product of the pressing force NF and the pressing angle WA exceeds 60.
[0626] According to the invention involved in (((13))), there is provided an image forming method in which colorant filming on the surface of the image holder is suppressed and wear of the cleaning scraper is suppressed, compared to a cleaning process including using a cleaning scraper in which the total amount of F and Si present within 200nm from the surface in contact with the image holder is less than 75% of the total amount of F and Si present within 5μm from the surface.
[0627] The above-mentioned embodiments of the present invention are provided for the purpose of illustration and description. In addition, the embodiments of the present invention do not fully and exhaustively include the present invention, and do not limit the present invention to the disclosed methods. Obviously, various modifications and changes are self-evident to those skilled in the art to which the present invention belongs. The present embodiment is selected and described in order to most easily understand the principles of the present invention and its application. Thus, other technicians in the art can understand the present invention through various variations optimized for specific uses assumed to be various embodiments. The scope of the present invention is defined by the above claims and their equivalents.
[0628] Explanation of symbols
[0629] 1-undercoat layer, 2-charge generating layer, 3-charge transporting layer, 4-conductive substrate, 7A, 7-electrophotographic photoreceptor, 8-charging device, 9-exposure device, 11-developing device, 13-cleaning device, 14-lubricant, 40-transfer device, 50-intermediate transfer body, 100-image forming device, 120-image forming device, 131-cleaning blade, 132-fibrous component (roller-shaped), 133-fibrous component (flat brush-shaped), 300-processing box.
Claims
1. An image forming device comprising: Image holding body; a charging member for charging the surface of the image holding member; an electrostatic latent image forming member for forming an electrostatic latent image on the charged surface of the image holding member; A developing member containing an electrostatic latent image developer containing a toner having toner particles, wherein a release agent existing in a region within 800 nm from the surface of the toner particles accounts for 70% or more of the entire release agent of the toner particles, and a melting temperature of the release agent is 65° C. or more and 80° C. or less, and an electrostatic latent image formed on the surface of the image holding member is developed into a toner image by the electrostatic latent image developer; a transfer member for transferring the toner image formed on the surface of the image holding body to the surface of a recording medium; and A cleaning device having a cleaning scraper which contacts and cleans the outer peripheral surface of the image holder and is made of a polyurethane resin, wherein the total amount of F and Si present within 200 nm from the surface in contact with the image holder accounts for more than 75% of the total amount of F and Si present within 5 μm from the surface.
2. The image forming apparatus according to claim 1, wherein: The releasing agent existing in a region within 800 nm from the surface of the toner particle accounts for 75% or more of the releasing agent in the entire toner particle.
3. The image forming apparatus according to claim 1 or 2, wherein: The melting temperature of the release agent is 70° C. or higher and 75° C. or lower.
4. The image forming apparatus according to any one of claims 1 to 3, wherein: The 100% modulus at 23° C. of the surface of the cleaning blade in contact with the image holding body is 11 MPa or more and 22 MPa or less.
5. The image forming apparatus according to claim 4, wherein: The 100% modulus at 23° C. of the surface of the cleaning blade in contact with the image holding body is 15 MPa or more and 18 MPa or less.
6. The image forming apparatus according to any one of claims 1 to 5, wherein: In the cleaning blade, the total amount of F and Si present within 200 nm from the surface in contact with the image holding member accounts for 85% or more of the total amount of F and Si present within 5 μm from the surface.
7. The image forming apparatus according to any one of claims 1 to 6, wherein: In the cleaning blade, a total amount of F and Si present on a surface in contact with the image holding member is 15 atm % or more.
8. The image forming apparatus according to claim 7, wherein: In the cleaning blade, a total amount of F and Si present on a surface in contact with the image holding member is 18 atm % or more and 25 atm % or less.
9. The image forming apparatus according to any one of claims 1 to 8, wherein: In the cleaning blade, the total amount of F and Si present at a position 50 nm from the surface in contact with the image holding member is 0.3 atm % or more.
10. The image forming apparatus according to claim 9, wherein: In the cleaning blade, a total amount of F and Si present at a position 50 nm from a surface in contact with the image holding member is 1.0 atm % or more and 2.0 atm % or less.
11. The image forming apparatus according to any one of claims 1 to 10, wherein: The cleaning blade contains a silicone-based polymer in a surface layer that contacts the image holding member.
12. The image forming apparatus according to any one of claims 1 to 11, wherein: A product of a static pressing force NF and a pressing angle WA between the cleaning blade and the image holding member is 40° or more and 60° or less.
13. An image forming method, comprising: A charging process to charge the surface of the image holding body; An electrostatic latent image forming step of forming an electrostatic latent image on the charged surface of the image holding member; A developing step of developing the electrostatic latent image formed on the surface of the image holding member into a toner image by an electrostatic latent image developer, wherein the electrostatic latent image developer contains a toner having toner particles, wherein a release agent present in an area within 800 nm from the surface of the toner particles accounts for 70% or more of the release agent in the entire toner particles, and the melting temperature of the release agent is 65° C. or more and 80° C. or less; a transfer step of transferring the toner image formed on the surface of the image holding body to the surface of a recording medium; and The cleaning process involves contacting a cleaning blade with the peripheral surface of the image holder and cleaning it, wherein the cleaning blade is made of a polyurethane resin, and the total amount of F and Si within 200 nm of the surface in contact with the image holder accounts for more than 75% of the total amount of F and Si within 5 μm of the surface.
Citation Information
Patent Citations
Cleaning blade, cleaning device, and image forming apparatus
JP2005345493A
Cleaning blade and electrophotographic image forming device using the same
JP2010102327A